Comparative analysis of cow and buffalo milk based probiotic yoghurt formulations, for physicochemical, sensory, and in vitro biological activities - Muhammad Azhar Iqbal; Mian Anjum Murtaza; Aysha Sameen; Iram Hafiz; Ashiq Hussain; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Fakhria A. Al-Joufi (Food and Humanity, 2026)

Mutation mapping and functional characterization of a missense mutation p.Arg228Cys in ALDH3A2 gene causing Sjögran-Larson syndrome - Muhammad Zeeshan Ali; Samia Sattar; Abdulfatah M. Alayoubi; Shakil Abbas; Mohammed Turki Hussain Alharthi; Alwaleed Fahad H. Altemani; Muhammad Latif; Muzammil Ahmad Khan; Christian Windpassinger (Molecular Biology Reports, 2026)

Comparative Analysis of Polymeric and Lipid Polymer Hybrid Nanoparticles: In-Vitro and In-Vivo Analysis for Pulmonary Delivery of Atorvastatin - Kifayat Ullah Shah; Muhammad Usama Ghani Khan; Fahad Y. Sabei; Muhammad Danish Saeed; Firdous Ahmad Burki; Muhammad Yasir Ghani Khan; Awaji Y. Safhi; Ahmad Salawi; Abdullah Alsalhi; Ali Hanbashi (Journal of Pharmaceutical Innovation, 2026)

Phytochemical Analysis, Antioxidant and Pharmacological Evaluation of Antidiabetic Activity of Methanolic Extract of Geranium wallichianum D. Don ex Sweet in Alloxan-Induced Diabetic Rats - Fatima Afzal; Abdul Aleem; Javed Iqbal; Fahad Asim; Irfan Anjum; Muhammad Naveed Mushtaq (Journal of Pharmaceutical Innovation, 2026)

Geophysical and remote sensing insights into tectonics and mineralization of Hattian, Azad Jammu and Kashmir - Shahid Ahmed; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Khawaja Umair Majeed; Junaid Yousif (Journal of Applied Geophysics, 2026)

Nanoplastic removal from water using metal–organic framework-based adsorbents and membrane systems: Mechanisms, performance, and practical perspectives - Muhammad Fahad Tariq; I. Ihsanullah; Farhan Javed; Ismail W. Almanassra; Muataz Ali Atieh (Journal of Water Process Engineering, 2026)

Achieving high-quality and safe compost: a study on multi-optimization of a non-linear system using machine learning - Yuchang Shi; Muhammad Fahad Sardar; Longmei Qiu; Binxu Li; Muhammad Zia-ur-Rehman; Yukun Xue; Xu Zhang; Wuyang Zhao; Hongna Li (Bioresource Technology, 2026)

Retraction Note: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2026)

Assessing the role of Plant Growth-Promoting Bacteria (PGPB) in salt stress tolerance of tomato crop: a global meta-analysis - Muhammad Wasif; Muhammad Fahad Nadeem; Muhammad Awais Ghani (Plant and Soil, 2026)

Long-term PM2.5 exposure and timing of pubertal development in boys and girls: A prospective cohort study in Chongqing, China - Liling Xie; Jingwei Li; Xizou An; Haiying Zhong; Wenbing Luo; Muhammad Fahad Tahir; Shunqing Luo; Cui Song; Xiaohua Liang (Environmental Research, 2026)

Ratemaking under indexation: How policy clauses compound into retail electricity tariffs - Fahad Bin Abdullah; Muhammad Arsalan Aqeeq; Falak Shad Memon; Maria Abdullah; Sumaira Chamadia (Utilities Policy, 2026)

Retraction notice to “Effects of dumpsite leachate plumes on surface and groundwater and the possible public health risks” [Sci. Total Environ. 897 (2023) 165469] - Joseph Omeiza Alao; Abubakar Fahad; Hazem Ghassan Abdo; Daniel A. Ayejoto; Hussin Almohamad; Muhammad Sani Ahmad; Mohammed Shettima Nur; Theophilus Toro Danjuma; Mumeen Adebayo Yusuf; Olaleye Timilehin Francis; Alao Ovaioza Joy (Science of The Total Environment, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Evaluation of the antiulcer activity of methanolic extract of Bidens biternata on experimental rats via involvement of the PGE2/Nrf2/HO-1/NF-κB/Caspase-3 pathways - Muhammad Murtaza; Mohammad Khalid; Gaurav Gupta; Haider Ali; Kavita Goyal; Adil Abalkhail; Fahad M. Aldakheel; Farhan R. Khan; Ameeduzzafar Zafar (South African Journal of Botany, 2026)

NDVI-based vegetation monitoring and forecasting in Madinah (2014–2050) under the Saudi Green Initiative (SGI); using Google earth engine - Muhammad Shahab; Fahad Alshehri; Huma Shakoor (Urban Climate, 2026)

Applications of machine learning in enhancing evaporation estimation for small reservoirs: a case study in semi-arid South Texas - Syed Muhammad Fahad Abdullah; Chu-Lin Cheng; Jude Benavides; Jungseok Ho; Rafael M. Almeida (Modeling Earth Systems and Environment, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Trends in emerging analytical strategies for okadaic acid detection in aquatic food commodities - Muhammad Saleem; Md Mehedi Hassan; Waqas Ahmad; Liang Tian; Muhammad Fahad Khan; Faiz-ul-Hassan Shah; Yi Xu; Quansheng Chen (Trends in Food Science & Technology, 2026)

Unraveling oak diversity: molecular characterization and phylogenetic relationships of Quercus species from the western Himalayas - Ayesha Azeem; Daniel Potter; Abdul Majid; Sajjad Sajjad; Khushi Muhammad; Irfan Ullah; Asif Khan; Abdulwahed Fahad Alrefaei; Sajid Ali (Plant Systematics and Evolution, 2026)

Comprehensive genomic and haplotype analysis of the phytocyanin gene family reveals evolutionary expansion and functional diversification in Setaria italica - Muhammad Rashid; Muhammad Fahad; Liang Wu; Yuxin Shen (Plant Cell Reports, 2026)

Spirulina supplementation and human health: An umbrella review of meta-analysis on randomized controlled trials - Nazila Soufi Amlashi; Fahad Rajab Mahmood; Mirza R. Baig; Tina Saeed Basunduwah; Pareshkumar N. Patel; Gulsara Ruziyeva; Gunjan Singh; Muhammad Shahid Iqbal; Munthar Kadhem; Amirali Ebrahimi (Algal Research, 2026)

Corrigendum to “global research on the air quality status in response to the electrification of vehicles” [Science of the Total Environment, 795, (2021), 148861] - Yansong Bao; Khalid Mehmood; Saifullah; Muhammad Yaseen; Saad Dahlawi; Muhammad Mohsin Abrar; Shah Fahad (Science of The Total Environment, 2026)

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Carboxylated Graphene Oxide (CGO) Adsorbent as an Effective and Green Approach for Targeting As (III) with Improved Adsorption Characteristics - Khizar Hussain Shah; Gul Afshan Khan; Zaher Hashisho; Sadaf Sarfraz; Muhammad Fahad; Muhammad Kazim (Water, Air, & Soil Pollution, 2026)

Arginine-Dependent Defense Actions in Rice (Oryza Sativa L.) Against Microplastic Contaminated Root Zone - Modhi O. Alotaibi; Naila Hadayat; Mohamed O. Alshahrani; Muhammad Kashif Irshad; Anees Manzoor; Nahaa M. Alotaibi; Fahad Mohammed Alzuaibr; Suliman Mohammed Suliman Alghanem; Omar Mahmoud Alzoubi; Jeddi Kaouthar; Saher Nawaz (Journal of Soil Science and Plant Nutrition, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Closing the loop in concrete production: A dual-waste valorization pathway using rice husk ash and extracted micro silica - Muhammad Fahad Ullah; Hesheng Tang (Sustainable Chemistry and Pharmacy, 2026)

Understanding green house gases emission dynamics from forest fires in Thailand using predictive models - Fahad Shahzad; Kaleem Mehmood; Shoaib Ahmad Anees; Muhammad Adnan; Khadim Hussain; Waseem Razzaq Khan; Munawar Shah; Punyawi Jamjareegulgarn; Manuela Oliveira; José G. Borges (Global and Planetary Change, 2026)

Growth and Phytostabilization Potential of Willow under Rare Earth Elements Exposure in Floating Treatment Wetlands - Muhammad Mohsin; Muhammad Ramzan; Edita Baltrėnaitė-Gedienė; Nicole Nawrot; Erik Kaipiainen; Fahad Rasheed; Zikria Zafar; Ewa Wojciechowska; Ari Pappinen; Suvi Kuittinen (Water, Air, & Soil Pollution, 2026)
Phytoremediation of contaminated freshwater bodies with rare earth elements (REEs) is a promising nature-based solution, but it is rarely studied. Here, we studied how efficiently willow ( Salix schwerinii: SS ) and cultivar (Klara: KL) purify water and react to three combined doses of REEs. SS and KL were subjected to increasing combined doses of REEs, specifically lanthanum (La) and neodymium (Nd), for 8 weeks in floating treatment wetlands (FTWs). The treatments included: T0 (tap water without REEs), T1 (10 µM La + 10 µM Nd), T2 (20 µM La + 20 µM Nd), and T3 (40 µM La + 40 µM Nd). The study aimed to evaluate how La and Nd affect willow growth, including height, dry biomass, and tolerance index, as well as their uptake and translocation within the roots, stems and leaves. Results showed that willow height increased over time, with significant biomass development and a noticeable allocation to stem biomass under REEs exposure. Height and biomass tolerance indices indicated that SS and KL exhibited high tolerance to REEs. The findings revealed the highest accumulation of La (25,252 μg plant −1 ) and Nd (18,252 μg plant −1 ) in the roots of SS in treatment T3. KL also showed the highest accumulation of La (16,153 μg plant −1 ) and Nd (13,209 μg plant −1 ) in roots, but in treatment T2. Moreover, SS and KL demonstrated increased translocation of La and Nd, particularly from the water solution to the roots, with minimal translocation to the leaves and stems. In SS, La and Nd removal efficiencies ranged from 56–95% and 40–74%, respectively. For KL, La removal varied from 22–90%, while Nd removal ranged from 21–68%. A considerable accumulation of nutrients such as P, K, Mg, and Ca in the willow tissues was also observed. Further research is needed to evaluate the long-term removal and recovery of REEs by willow and other perennial plants, with a primary focus on environmental factors and design of FTWs which may influence the uptake and translocation of REEs in plants.

Enhancing Lodging Resistance in Rapeseed Strategies for Sustainable Agriculture and Yield Improvement - Shahid Ullah Khan; Umer Mahmood; Muhammad Sirab Khan; Minchao Qian; Shengting Li; Osama Alam; Yonghai Fan; Hui Wang; Wei Chang; Hameed Gul; Shah Fahad; Kun Lu (Journal of Plant Growth Regulation, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

A review on CO2 mineralization in saline aquifers: Advances, challenges, and future prospects for sustainable carbon sequestration - Arshad Khan; Fahad Khan; Tatenda Raphinos Marapira; Saad Alafnan; Arshad Raza; Mohamed Mahmoud; Muhammad Shahzad Kamal (Journal of Environmental Management, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Genetic Innovations in Soybean: Key Genes Driving Salinity Tolerance - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Ali Muhammad; Ehsan Ali; Sajjad Ali; Shah Fahad; Xianzhong Feng (Journal of Plant Growth Regulation, 2026)

Effect of the landscape composition of artificial Robinia pseudoacacia forests on bird diversity in the Loess Plateau - Zixin Wang; Xingyan Jian; Long Li; Wanrong Cheng; Luhui Ai; Xiang Li; Jawaher Alkahtani; Muhammad Fahad Sardar (Agriculture, Ecosystems & Environment, 2026)

Integrated water and nitrogen management sustains rice yield and efficiency under changing climate scenarios - Fazli Hameed; Muhammad Mannan Afzal; Anis Ur Rehman Khalil; Junzeng Xu; Shah Fahad Rahim; Raheel Osman; Khalil Ahmad; Yongqiang Li; Tangyuan Ning (Agricultural Systems, 2026)

Biochar and plant growth-promoting rhizobacteria: a promising combination enhancing wheat (Triticum aestivum L.) growth under chromium stress - Fazal Jalal; Awais Ahmad; Aqib Iqbal; Zafar Hayat Khan; Shah Fahad; Nazia Tahir; Fazal Said; Muhammad Imtiaz; Muhammad Ali Khan; Sayed Hussain; Attaur Rahman; Wasim Khan; et al. (Rhizosphere, 2025)

Modelling of electrolyzers and fuel cells for grid services under high RES penetration - Sulaiman S. Ahmad; Abdullah A. Almehizia; Muhammad Khalid; Fahad Saleh Al-Ismail (Next Research, 2025)

Bacterial polysaccharides in the food industry: Synthesis-structure-properties relationships, AI-driven innovations, regulatory challenges, and bioeconomy prospects - Muhammad Wajid Ullah; Sehrish Manan; Khulood Fahad Alabbosh; Mazhar Ul-Islam; Omar Mohammad Atta; Asif Ali Khan; Yimin Fan; Khalid Ali Khan; Noureddine Elboughdiri; Zhiguo Wang (Carbohydrate Polymers, 2025)

Assessment of tourist littering behavior using an innovative monitoring technique at No. 1 bathing Beach, Qingdao, China - Rashid Pervez; Chao Jia; Marium Sardar; Zafar Ullah Jattak; Jawad Ali; Muhammad Fahad Sardar; Zhongping Lai (Journal of Coastal Conservation, 2025)

Mechanical characterization and impact resistance of concrete incorporating recycled thin-walled hollow tubular GFRP sections - Muhammad Rizwan Riaz; Muhammad Moeed Azhar; Muhammad Fahad Ejaz; Rizwan Azam; Muhammad Faraz Javaid (Innovative Infrastructure Solutions, 2025)

Potential of green nanotechnology for air pollution and microplastic remediation in China: evidence by ARDL panel data analysis - Muhammad Fahad Sardar; May Bin-Jumah; Hassan A. Rudayni; Ahmed A. Allam; Weihua Guo (Clean Technologies and Environmental Policy, 2025)

Postharvest Challenges in Improving Peach Quality Using 1-Methylcyclopropene, Calcium Chloride, Peach Gum, and Refrigeration - Qurratulain Bashir Khan; Taufiq Nawaz; Muhammad Jahangir; Muhammad Liaquat; Tanzeel Ur Rahman; Shah Fahad; Abdul Sattar Shah; Shehla Sammi (Applied Fruit Science, 2025)

Chitosan induces water deficit stress tolerance in Gladiolus grandiflorus via regulating water relations, gaseous exchange traits, and antioxidative defense - Muhammad Rizwan; Gulzar Akhtar; Muhammad Asif Shehzad; Salman Aloufi; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; M. Nasir Khan; Özhan Şimşek; Fahad Al-Asmari; Mehmet Tütüncü; Tolga İzgü; Lala Gurbanova (Plant Biosystems, 2025)

Corrigendum to “Purification and structural analysis of tannase from novel bacteria of Bacillus cereus strain KMS3-1 isolated in marine sediment” [Food Bioscience 61 (2024) 104664] - Rasiravathanahalli Kaveriyappan Govindarajan; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Chartchai Khanongnuch; Alagarsamy Vasanthakumar; Gangalla Ravi; Douglas J.H. Shyu; Muhammad Fazle Rabbee; Maximilian Lackner (Food Bioscience, 2025)

Bcl-2-Associated Athanogene (BAG) Co-chaperones: Key Players in Multiple Abiotic and Biotic Stress Tolerance in Plants - Muhammad Arif; Shuzhen Men; Ayesha Fazal Nawaz; Xin Li; Ling Xu; Xuemin Yang; Shah Fahad; Parvaiz Ahmad; Ruhong Xu; Luhua Li (Journal of Plant Growth Regulation, 2025)

Enhancing mechanical and durability properties of bentonite-modified self-compacting concrete - Khawaja Adeel Tariq; Aashir Waleed; Jamil Ahmad; Fahad Ali; Naveed Ahmad; Muhammad Danish Nisar (Innovative Infrastructure Solutions, 2025)

Metabolite characterization of probiotic Enterococcus Faecium for targeting Salmonella Entrica gut bacteria causing gastroenteritis - Kashef Choudhary; Muhammad Naveed; Tariq Aziz; Syeda Izma Makhdoom; Muhammad Waseem; Nada K. Alharbi; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A. Alhhazmi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Spatio-temporal variability study of Shigar Basin Glaciers, Central Karakoram Region, Pakistan - Salman Mustafa; Faisal Rehman; Adnan Shafiq Rana; Tahir Azeem; Omar Riaz; Muhammad Fahad Ullah; Jamil Siddique; Faisal Rehman (Environmental Monitoring and Assessment, 2025)

Effect of erucic acid against DMBA-induced breast cancer via inflammatory/apoptosis pathway - Abdulaziz Alamri; Fahad A. Al-Abbasi; Muhammad Afzal; May M. Alqurashi; Thamir M. Eid; Hayat M. Albishi; Ehssan Moglad; Nadeem Sayyed; Imran Kazmi (Food Bioscience, 2025)

Remarkable energy storage performance in lead-free tungsten bronze ferroelectrics for high temperature applications - Muhammad Fahad Riaz; Fayaz Hussain; Ali Dad Chandio; Zeshan Javed; Wenfeng Yue; Zhenhao Fan; Yuxiao Du; Bingsen Wang; Mohammad Abu Abdeen; Gulmurza Abdurakhmanov; Adil Alshoaibi; Yasemin Tabak; et al. (Chemical Engineering Journal, 2025)

Mathematical models for fluid flow in porous media with machine learning techniques for landfill waste leachate - Muhammad Sulaiman; Muhammad Salman; Ghaylen Laouini; Fahad Sameer Alshammari (Stochastic Environmental Research and Risk Assessment, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Kaempferol alleviates cypermethrin induced reproductive toxicity in rats via Nrf2-mediated antioxidant and apoptotic regulation with histopathological evidence: in vivo and in silico study - Fahad Kabeer; Shaista Anjum; Atique Ahmed Behan; Muhammad Usman; Nazima Yousaf khan; Muhammad Azeem; Hafiz Misbah Ud Din; Muhammad Adeel Arshad; Sadaf Nazir; Shiping Cheng; Jameel Ahmed Buzdar (Journal of Molecular Histology, 2025)

Image segmentation and machine learning modelling for water status determination and precision irrigation management - Hamza Salah Ud Din; Aqib Iqbal; Fazal Jalal; Awais Ahmad; Muhammad Haris Paracha; Shah Fahad; Zafar Hayat Khan; Shah Saud; Taufiq Nawaz (Journal of Crop Science and Biotechnology, 2025)

Liver response to heat and humidity stress in high fat diet fed rats: a biochemical and histological investigation - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad ur Rahman; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Sifa Dai (International Journal of Biometeorology, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Ripeness Grading for Mango Packaging by Fusion of Deep Features - Muhammad Imran; Syed Fahad Tahir; Labiba Gillani Fahad (Applied Fruit Science, 2025)

Molecular Simulation and Expression Analysis of Vitamin C and Curcumin in Mitigating Buprofezin-induced Genotoxicity and Inflammatory Responses in Balb/c Mice - Haleema Sadia; Irfan Zia Qureshi; Muhammad Naveed; Tariq Aziz; Manal F. Elkhadragy; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A Alhhazmi; Hanan Abdulrahman Sagini; Suad Hamdan Almasoudi; Fakhria A. Al-Joufi (Cell Biochemistry and Biophysics, 2025)

Artificial intelligence and companion animals: Perspectives on digital healthcare for dogs, cats, and pet ownership - Muhammad Furqan Arshad; Fahad Ahmed; Francesca Nonnis; Claudia Tamponi; Antonio Scala; Antonio Varcasia (Research in Veterinary Science, 2025)

New paradigms to evaluate the stratigraphy for the geological and geoarchaeological prospects of the upper and post-Siwaliks in the Soan Valley, Upper Indus Basin, Pakistan - Nadir Fawad; Daidu Fan; Taixun Liu; Anne Dambricourt Malassé; Muhammad Kamran; Qazi Adnan Ahmed; Fahad Ali (Quaternary International, 2025)

Isolation, Identification, biochemical and molecular characterization of potential source of enterotoxigenic strains of Staphylococcus aureus from the bovine raw and mastitis milk - Sikander Ali; Farzana Nazir; Muhammad Usman Ahmad; Hira Sarfraz; Abid Sarwar; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Areej A. Alhhazmi; Abeer M. Alghamdi; Fakhria A. Al-Joufi (International Dairy Journal, 2025)

Corrigendum to “Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction” [363 (2024) 130919] - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2025)

Spatiotemporal dynamics and environmental drivers of fractional vegetation cover in a Semi-Arid region using machine learning - Shoaib Ahmad Anees; Kaleem Mehmood; Sultan Muhammad; Mi Luo; Fahad Shahzad; Waseem Razzaq Khan (Theoretical and Applied Climatology, 2025)

Evolving climatic patterns and drought risk in Pakistan’s agro-ecological zones - Raja Muhammad Usama; Sawaid Abbas; Mansour Almazroui; Muhammad Fahad Bilal; Asad Ali (Theoretical and Applied Climatology, 2025)

Balancing Nitrogen Application to Enhance Soil Health and Mitigate Heavy Metal Contamination Risks in Sweet Potato Cultivation - Rafiq Ahmad; Cheng-cheng Si; Shah Fahad; Wajid Ali Khattak; Muhammad Zakir (Journal of Soil Science and Plant Nutrition, 2025)

Unlocking the Geoheritage Potential of Hingol National Park (HNP), Pakistan: Geological and Geomorphological Insights Through Multi-Satellite Remote Sensing Data and Field Geology Validation - Muhammad Yaseen; Rujun Chen; Jawad Ahmad; Shahid Ali Shah; Shah Fahad; Muhammad Naveed Anjum; Syed Tanvir Shah (Geoheritage, 2025)

Advancing forest fire prediction: A multi-layer stacking ensemble model approach - Fahad Shahzad; Kaleem Mehmood; Shoaib Ahmad Anees; Muhammad Adnan; Sultan Muhammad; Ijlal Haidar; Jamshid Ali; Khadim Hussain; Zhongke Feng; Waseem Razzaq Khan (Earth Science Informatics, 2025)

Microbial transformation: the role of fermentation in advancing nutritional quality and human health - Babar Iqbal; Khulood Fahad Alabbosh; Abdulkareem Raheem; Inam Ullah; Ali Raza Khan; Muhammad Sohail Memon (Archives of Microbiology, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Electrokinetic treatment at the thermophilic stage achieves more effective control of heavy metal resistance in swine manure composting - Binxu Li; Xu Zhang; Tingting Song; Muhammad Fahad Sardar; Yuchang Shi; Changxiong Zhu; Hongna Li (Journal of Environmental Management, 2025)

Biogenic amines in honey bee cognition: neurochemical pathways and stress impacts - Muhammad Fahad Raza; Wenfeng Li (Current Opinion in Insect Science, 2025)

Electrochemical activation of alum sludge for the adsorption of lead (Pb(II)) and arsenic (As): Mechanistic insights and machine learning (ML) analysis - Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Jong-Gook Kim (Bioresource Technology, 2025)

Regulation of Apoptotic Pathways by MicroRNAs: A Therapeutic Strategy for Alzheimer’s Disease - Mohamed J. Saadh; Faris Anad Muhammad; Tuqa S. Alazzawi; Ali A. Fahdil; Zainab H. Athab; Jamshid Tuxtayev; Fahad Alsaikhan; Bagher Farhood (Molecular Neurobiology, 2025)

Investigation of the physical properties of expanded shale aggregate and its influence on the mechanical properties of OPC and LC3-50-based concretes - Syed Muhammad Fahad Hussain; Tehmina Ayub; Sadaqat Ullah Khan; S. F. A. Rafeeqi (Innovative Infrastructure Solutions, 2025)

Translational potential of GADD45α: biomarker and therapeutic target in age-associated neurodegeneration and longevity - Imran Kazmi; Fahad A. Al-Abbasi; Mustafa Zeyadi; Misbahuddin Rafeeq; Alaa Hamed Habib; Johar Iqbal; Sami I. Alzarea; Omar Awad Alsaidan; Muhammad Shahid Nadeem (Biogerontology, 2025)

Impact of Climatic Variables on Fruit Bearing Behavior and Disease Incidence in Commercial Mango Cultivars in a Semi-arid Region - Hafiz Mohkum Hammad; Talal Tariq; Shafqat Saeed; Muhammad Tariq Malik; Hafiz Faiq Siddique; Rashid Jawad; Shah Fahad; Ifrah Kanwal; Aitazaz A. Farooque (Applied Fruit Science, 2025)

Finding the Best Growth Media for Kiwifruit Cv. ‘Hayward’ Seedling Rootstocks in Mansehra District, Pakistan - Sadaf Bibi; Aftab Afzal; Ghulam Mujtaba Shah; Abdul Waheed; Muhammad Anas; Waseem Ahmed Khattak; Shah Fahad (Applied Fruit Science, 2025)

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Advancements in the production methods and recycling of multilayer plastics with sustainable applications: A comprehensive review - Maha Awjan Alreshidi; Krishna Kumar Yadav; G. Shoba; Amel Gacem; S. Padmanabhan; T. Vinod Kumar; Ahmed M. Fallatah; Javed Khan Bhutto; Fahad M. Aldosari; Manawwer Alam; Muhammad A. Abo El-Khair; P. Tamizhdurai; et al. (Chemical Engineering Journal, 2025)

Omics Technologies: Unraveling Abiotic Stress Tolerance Mechanisms for Sustainable Crop Improvement - Muhammad Hamzah Saleem; Sana Noreen; Izwa Ishaq; Ammara Saleem; Khalid Ali Khan; Sezai Ercisli; Muhammad Anas; Awais Khalid; Temoor Ahmed; Ammara Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

An integrated comprehensive approach describing structural features and comparative petrophysical analysis between conventional and machine learning tools to characterize carbonate reservoir: A case study from Upper Indus Basin, Pakistan - Zohaib Naseer; Urooj Shakir; Muyyassar Hussain; Qazi Adnan Ahmad; Kamal Abdelrahman; Muhammad Fahad Mahmood; Mohammed S. Fnais; Muhsan Ehsan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Restoring wheat productivity and nutrient balance under cadmium stress through reducing toxicity, metal uptake, and oxidative damage using selenium nanoparticles - Ayesha Jamil Abbasi; Muhammad Anas; Minhas Elahi; Amjid Khan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Shah Fahad; Hosam O. Elansary; Eman A. Mahmoud; Temoor Ahmed; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Simultaneous removal of Cr(VI), As(III), and sulfanilamide via an e-barrier electrochemical system: A pilot study - Jong-Gook Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Spatial and temporal vegetation dynamics from 2000 to 2023 in the Western Himalayan regions - Kaleem Mehmood; Shoaib Ahmad Anees; Sultan Muhammad; Gadah Albasher; Fahad Shahzad; Khadim Hussain; Qijing Liu; Rashid Ayub; Waseem Razzaq Khan (Stochastic Environmental Research and Risk Assessment, 2025)

Geophysical Study of Crustal Deformation Using Gravity Data: Muzaffarabad and Adjoining Regions in Azad Jammu and Kashmir - Arooj Zulqranan; Michal Šprlák; Muhammad Rustam Khan; Fahad Hameed (Pure and Applied Geophysics, 2025)

Individual and Combinatorial Applications of Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Increase Morpho-Physio-Biochemical Responses in Rice (Oryza sativa L.) under Cadmium Stress - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Faran Tahir; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Mohammed O. Alshaharni; Eman Fayad; Khalid Ali Khan; Awais Khalid; Shafaqat Ali; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Inheritance of Cell Membrane Stability and Yield Components Under Drought and Salinity Stress in Bread Wheat (Triticum aestivum L.) - Sameena Naqi; Aamir Hamid Khan; Rashid Mehmood Rana; Muhammad Imran Hamza; Marcin Kiedrzyński; Muhammad Naveed Tahir; Munir Ahmad; Shah Saud; Shah Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Integrated geophysical and hydrogeological techniques for environmental monitoring and assessment: a case study for waste disposal site, Jeddah Saudi, Arabia - Faisal Rehman; Helmy S. O. Abuelnaga; Hussein M. Harbi; Tahir Azeem; Jamil Siddique; Omar Riaz; Muhammad Fahad Ullah; Faisal Rehman (Arabian Journal of Geosciences, 2025)

Efficacy of ascorbic acid coated quantum dots in alleviating lead-induced oxidative damage and enhancing growth parameters in rice (Oryza sativa L.) for sustainable cultivation - Aliza Falak; Muhammad Anas; Amjid Khan; Alvina Hayat; Zeenat Shaheen; Muhammad Hamzah Saleem; Shah Fahad; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Textile wastewater treatment by heterogeneous catalytic ozonation using microcellulose loaded ZIF 67 catalyst - Muhammad Fahad Tariq; Farhan Javed; Luigi Rizzo; Muhammad Wasim Tahir; Amir Ikhlaq (Journal of Environmental Management, 2025)

Self-nanoemulsifying drug delivery system for nebulization: fabrication and evaluation for systemic delivery of atorvastatin - Muhammad Danish Saeed; Kifayat Ullah Shah; Muhammad Fahad; Shefaat Ullah Shah; Syed Faisal Badshah; Hassan Shah; Irfan Anjum; Gamal A. Shazly; Mohammed Bourhia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Biology and predation of the Chrysoperla carnea (Stephens) (Insecta: Neuroptera: Chrysopidae) feeding on two important spider mite pests (Acari: Tetranychidae) under low humidity - Muhammad Waleed Shakoor; Muhammad Kamran; Fahad Jaber Alatawi (Experimental and Applied Acarology, 2025)

Heavy Metal Concentrations in Water, Sediment, and Fish Species in Chashma Barrage, Indus River: A Comprehensive Health Risk Assessment - Khalid Hussain Rind; Sonia Aslam; Nazakat Hussain Memon; Asif Raza; Muhammad Qamar Saeed; Alia Mushtaq; Javed Ahmed Ujan; Syed Fahad Habib; Salim S. Al-Rejaie; Mohamed Mohany (Biological Trace Element Research, 2025)

Advancing Chickpea Breeding: Omics Insights for Targeted Abiotic Stress Mitigation and Genetic Enhancement - Muhammad Tanveer Altaf; Waqas Liaqat; Amjad Ali; Amna Jamil; Muhammad Fahad; Muhammad Aneeq Ur Rahman; Faheem Shehzad Baloch; Heba I. Mohamed (Biochemical Genetics, 2025)

Highly efficient phosphate extraction from water using bio-composites of nano zero valent iron supported on orange peel powder (nZVI@OPP): performance evaluation and mechanistic insights - Fahad Nadeem; Muhammad Ali Inam; Rashid Iftikhar; Safi Ullah Gill; Hira Amjad (Environmental Science and Pollution Research, 2025)

Coastal guardian: mangroves in Pakistan at risk from microplastic threats jeopardizing their crucial role in global CO2 dynamics - Tariq Mehmood; David Janke; Gajendra Kumar Gaurav; Muhammad Fahad Sardar (Environmental Science and Pollution Research, 2025)

Blood, feathers, and eggs as bioindicators of selenium sources and their impact on DNA damage in Japanese quails (Coturnix japonica) - Aimen Khalid; Sania Satti; Anqash Ayyub; Faisal Nawab; Muhammad Tahir; Shabana Naz; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Demilade Israel Ibiwoye (Research in Veterinary Science, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Geospatial assessment of climate variability and drought patterns: a case study from Pakistan - Sher Shah Hassan; Muhammad Arif Goheer; Humera Farah; Faiza Hafeez; Khurram Sheraz; Javaria Fahad; Aqil Tariq (Theoretical and Applied Climatology, 2025)

RETRACTED ARTICLE: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2025)

Exogenous application of melatonin and jasmonic acid protects the sugar beet from heat stress by modulating the enzymatic antioxidants deference mechanism and accumulation of organic osmolytes - Muhammad Irfan; Ahmed Abou El-Yazied; Muhammad Sheeraz; Shabir Hussain; Abdul Sattar; Qasim Ali; Hany G. Abd El-Gawad; Fahad Mohammed Alzuaibr; Maha Mohammed Alharbi; Siham M. Al-Balawi; Doaa Bahaa Eldin Darwish; Eldessoky S. Dessoky; et al. (Acta Physiologiae Plantarum, 2025)

Do structural and functional traits modulation determine the ecological fate of castor bean (Ricinus communis L.) under variable pedospheric and atmospheric conditions? - Ummar Iqbal; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (South African Journal of Botany, 2025)

Tailoring the electrochemical performance of rods-like Co-MOF: Fe-derived Co3O4: Fe electrodes for supercapacitor applications - Maryam Shah; Sonadia; Zoya Iqbal; Anwar Ul-Hamid; Muhammad Umair Mushtaq; Fahad Azad (Fuel, 2025)

Non-effervescent Polymeric Floating Tablets of Clarithromycin and Pantoprazole: Preparation and In-Vitro Evaluation for Improved Gastric Drug Retention - Fahad Ashraf; Kifayat Ullah Shah; Muhammad Danish Saeed; Faiqa Falak Naz; Fahad Y. Sabei; Tahseen Ahmed; Syed Shafqat Ali Shah; Amir Badshah; Naeem Ur Rehman; Kausar Ali Mahsud (Journal of Pharmaceutical Innovation, 2025)

Microbial Interactions and Bacterial Responses to Metal Stress in Plants: Mechanisms, Adaptations, and Applications for Sustainable Agriculture - Muhammad Anas; Aliza Falak; Sameel Hassan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Khalid Ali Khan; Awais Khalid; Shah Fahad (Journal of Crop Health, 2025)

Symbiotic Synergy: Unveiling Plant-Microbe Interactions in Stress Adaptation - Muhammad Anas; Awais Khalid; Muhammad Hamzah Saleem; Khalid Ali Khan; Waseem Ahmed Khattak; Shah Fahad (Journal of Crop Health, 2025)

Systematic implication of trichome morphology in alpine flora from Hindukush Mountain range - Muhammad Abdullah; Zahid Ullah; Syed Muhammad Iqbal Shah; Mushtaq Ahmad; Amjad Khan; Hussain Shah; Ateef Ullah; Shabir Ahmad; Mohammed Fahad Albeshr; Okezie Emmanuel; Hameed Ullah; Rahman Ali Khan (Genetic Resources and Crop Evolution, 2025)

Assessment of groundwater chemistry to predict arsenic contamination from a canal commanded area: applications of different machine learning models - Fazila Younas; Muhammad Fahad Sardar; Zahid Ullah; Jawad Ali; Xiaona Yu; Pengcheng Zhu; Weihua Guo; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Zhaojie Cui (Environmental Geochemistry and Health, 2025)

Fungicide resistance in Fusarium species: exploring environmental impacts and sustainable management strategies - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Muhammad Shahbaz; Aqleem Abbas; Fahad Hakim; Muhammad Shabbir; Yee Shin Tan; Jaya Seelan Sathiya Seelan (Archives of Microbiology, 2025)

Remediation of textile wastewater by hybrid technique using ZIF-67 catalyzed ozonation coupled with electrocoagulation - Farhan Javed; Muhammad Fahad Tariq; Amir Ikhlaq; Hafiz Muhammad Shahzad Munir; Ali Altaee (Journal of Water Process Engineering, 2025)

Association Between Serum Essential Metal Elements and Blood Pressure in Children: A Cohort Study - Muhammad Fahad Tahir; Xiaofei Wu; Yuwei Wang; Qin Liu; Xizhou An; Daochao Huang; Lijing Chen; Lanling Chen; Xiaohua Liang (Cardiovascular Toxicology, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

Characterization of mercury ameliorating rhizobacteria for enhancing growth and yield of Triticum aestivum L. in the field: An in-vitro and in- silico study - Aatif Amin; Muhammad Naveed; Sunbul Rasheed; Zakia Latif; Tariq Aziz; Fahad Al Asmari; Maha Aljabri (South African Journal of Botany, 2024)

Efficient removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) from aqueous solution using modified biochar: Preparation, performance, and mechanistic insights - Waqas Niaz; Dahai Zhang; Zia Ahmad; Nan Shen; Waqas Haider; Imran Ali; Muhammad Usman; Abdul Majid; Sheikh Fahad Javaid; Muhammad Ahsan Amjed; Xianguo Li (Journal of Environmental Chemical Engineering, 2024)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Artificial Intelligence-Based Classification of CT Images Using a Hybrid SpinalZFNet - Faiqa Maqsood; Wang Zhenfei; Muhammad Mumtaz Ali; Baozhi Qiu; Naveed Ur Rehman; Fahad Sabah; Tahir Mahmood; Irfanud Din; Raheem Sarwar (Interdisciplinary Sciences: Computational Life Sciences, 2024)
The kidney is an abdominal organ in the human body that supports filtering excess water and waste from the blood. Kidney diseases generally occur due to changes in certain supplements, medical conditions, obesity, and diet, which causes kidney function and ultimately leads to complications such as chronic kidney disease, kidney failure, and other renal disorders. Combining patient metadata with computed tomography (CT) images is essential to accurately and timely diagnosing such complications. Deep Neural Networks (DNNs) have transformed medical fields by providing high accuracy in complex tasks. However, the high computational cost of these models is a significant challenge, particularly in real-time applications. This paper proposed SpinalZFNet, a hybrid deep learning approach that integrates the architectural strengths of Spinal Network (SpinalNet) with the feature extraction capabilities of Zeiler and Fergus Network (ZFNet) to classify kidney disease accurately using CT images. This unique combination enhanced feature analysis, significantly improving classification accuracy while reducing the computational overhead. At first, the acquired CT images are pre-processed using a median filter, and the pre-processed image is segmented using Efficient Neural Network (ENet). Later, the images are augmented, and different features are extracted from the augmented CT images. The extracted features finally classify the kidney disease into normal, tumor, cyst, and stone using the proposed SpinalZFNet model. The SpinalZFNet outperformed other models, with 99.9% sensitivity, 99.5% specificity, precision 99.6%, 99.8% accuracy, and 99.7% F1-Score in classifying kidney disease. Graphical Abstract

Comparative assessment of pantothenic, aspartic, ascorbic and tartaric acids assisted Pb-phytoextraction by sunflower (Helianthus annuus L.) - Asif Ghafoor; Fahad Shafiq; Sumera Anwar; Lixin Zhang; Muhammad Ashraf (BioMetals, 2024)

Reliable attitude control integrating reaction wheels and embedded asymmetric magnetorquers for detumbling CubeSats - Shoaib Ahmed Khan; Zou Tao; Shah Fahad; Muhammad Salman; Mustafa Tahir; Anwar Ali (Advances in Space Research, 2024)

In Silico Identification and Characterization of Rare Cold Inducible 2 (RCI2) Gene Family in Cotton - Muhammad Fahad; Leeza Tariq; Muhammad Tanveer Altaf; Muhammad Shahnawaz; Mudassir Aslam; Waqas Liaqat; Inayat Ullah; Izhar Ullah; Heba I. Mohamed; Abdul Basit (Biochemical Genetics, 2024)

Molecular Characterization and Phylogenetic Analysis of Fasciola gigantica Based on ITS-1 Genetic Marker and copro-epidemiological Survey from Ruminants of Pakistan - Naunain Mehmood; Shafiah Zulfiqar; Hira Muqaddas; Muhammad Hasnain; Yadong Zheng; Habtye Bisetegn; Fahad Ahmed; Zafar Iqbal Khan; Furhan Iqbal (Acta Parasitologica, 2024)

Data-driven exploration in complex basins: A critical aspect of new prospect delineation in thin sands using simultaneous seismic inversion - Urooj Shakir; Aamir Ali; Muyyassar Hussain; Ahmed E Radwan; Ahmed Abd El Aal; Muhammad Raiees Amjad; Muhammad Fahad Mahmood (Journal of Earth System Science, 2024)

Effect of the combination of polyvinyl chloride (PVC) and steel slag waste on the durability and mechanical properties of composite mortars - Md. Alhaz Uddin; Numan Wali; Muhammad Tariq Bashir; Muhammad Ali Sikandar; Fahad Alsharari; Fayez Alanazi; Md. Munir Hayet Khan; Talal O. Alshammari (Innovative Infrastructure Solutions, 2024)

Assessing the stabilization impact of silica fume and phosphogypsum on hydro-mechanical characteristics of clayey sand - Muhammad Waleed; Fahad Alshawmar; Muhammad Abu-Bakr Jamil; Turab H. Jafri (Arabian Journal of Geosciences, 2024)

Assessing the electrode configuration in a sandbox system for the removal of sulfanilamide: A pilot study - Jong-Gook Kim; Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Chemosphere, 2024)

Ecotoxicological insights into the effects of triflumezopyrim on P. fuscipes fitness, detoxification pathways, and gene expression - Muhammad Musa Khan; Yuanzheng You; Dylan O'Neill Rothenberg; Pankaj Bhatt; Shah Fahad; Ying Zhou; Zeng-Rong Zhu (Chemosphere, 2024)

Ascorbic acid-mediated enhancement of antioxidants and photosynthetic efficiency: A strategy for enhancing canola yield under salt stress - Nawishta Saleem; Sibgha Noreen; Muhammad Salim Akhter; Mohammed O. Alshaharni; Habib-ur-Rehman Athar; Fahad Mohammed Alzuaibr; Omar Mahmoud Al-zoubi; Seema Mahmood (South African Journal of Botany, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Purification and structural analysis of tannase from novel bacteria of Bacillus cereus strain KMS3-1 isolated in marine sediment - Rasiravathanahalli Kaveriyappan Govindarajan; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Chartchai Khanongnuch; Alagarsamy Vasanthakumar; Gangalla Ravi; Douglas J.H. Shyu; Muhammad Fazle Rabbee; Maximilian Lackner (Food Bioscience, 2024)

Production and optimization of biofuels from locally isolated algal biomass: Strategies for circular economy integration - Muhammad Uzair Javed; Iqra Nazeer; Hamid Mukhtar; Umer Rashid; Maria J. Sabater; Fahad A. Alharthi (Biocatalysis and Agricultural Biotechnology, 2024)

Boron toxicity in plants: understanding mechanisms and developing coping strategies; a review - Shaopeng Zhao; Md. Enamul Huq; Shah Fahad; Muhammad Kamran; Muhammad Riaz (Plant Cell Reports, 2024)

Integrative approach to mitigate chromium toxicity in soil and enhance antioxidant activities in rice (Oryza sativa L.) using magnesium–iron nanocomposite and Staphylococcus aureus strains - Muhammad Azhar Ali; Muhammad Fahad Sardar; Afzal Ahmed Dar; Mohsin Niaz; Jawad Ali; Qian Wang; Yu Zheng; Yadan Luo; Gadah Albasher; Fengmin Li (Environmental Geochemistry and Health, 2024)

Impact of sea surface temperature in the Arabian Sea on the variability of Summer Monsoon Rainfall over Pakistan Region - Muhammad Adeel; Atteeq Razzak; Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal (Dynamics of Atmospheres and Oceans, 2024)

A Critical Review: Breeding Objectives, Genomic Resources, and Marker-Assisted Methods in Sorghum (Sorghum bicolor L.) - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Heba I. Mohamed; Muhammad Fahad; Muhammad Faheem Jan; Faheem Shehzad Baloch (Journal of Soil Science and Plant Nutrition, 2024)

Coactive Application of Bacillus Mycoides PM35 and Calcium Oxide Nanoparticles Stimulate Gene Expression Responses in Maize (Zea Mays L.) under Chromium Stress - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Sameera A. Alghamdi; Haifa Abdulaziz Sakit Alhaithloul; Sami Asir Al-Robai; Adel I. Alalawy; Fahad M. Alzuaibr; Abdulrahman Alasmari; Baber Ali; Muhammad Hamzah Saleem; Shah Fahad; Shafaqat Ali; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Waste Palm Leaves-Based Hydrochar Support Catalytic Esterification of Palm Fatty Acid Distillate - Muhammad Aliyu; Umer Rashid; Wan Azlina Wan Ab Karim Ghani; Mohamad Amran Mohd Salleh; Balkis Hazmi; Fahad A. Alharthi; Elsa Antunes; Jianglong Yu (BioEnergy Research, 2024)

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

Comparative analysis of physicochemical properties and biological activities of crude polysaccharides isolated from selected Auricularia cornea strains - Asif Ali Khan; Fang-Jie Yao; Feng-Jie Cui; Yu Li; Lixin Lu; Ismail Khan; Abdul Jalal; Ming Fang; Khulood Fahad Alabbosh; Mohamed F. Awad; Noureddine Elboughdiri; Muhammad Wajid Ullah (Food Bioscience, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

Advances in Physiochemical and Molecular Mechanisms of Abiotic Stress Tolerance in Plants - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Khalid Ali Khan; Sezai Ercisli; Mohsen Mohamed Elsharkawy; Shah Fahad (Journal of Crop Health, 2024)

Optimizing Micronutrient Supplementation in Mango Orchards for the Suppression of Mango Anthracnose (Colletotrichum gloeosporioides) - Wajid Nazir; Syed Atif Hasan Naqvi; Niaz Ahmed; Ateeq ur Rehman; Abdulwahed Fahad Alrefaei; Muhammad Asif Zulfiqar; Ummad ud Din Umar (Applied Fruit Science, 2024)

Efficient production of biodiesel from palm fatty acid distillate using a novel hydrochar-based solid acid catalyst derived from palm leaf waste - Muhammad Aliyu; Bryan R. Moser; Fahad A. Alharthi; Umer Rashid (Process Safety and Environmental Protection, 2024)

In-situ groundwater remediation of contaminant mixture of As(III), Cr(VI), and sulfanilamide via electrochemical degradation/transformation using pyrite - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2024)

Navigating the nexus: climate dynamics and microplastics pollution in coastal ecosystems - Afzal Ahmed Dar; Zhi Chen; Muhammad Fahad Sardar; Chunjiang An (Environmental Research, 2024)

Endophytic Bacillus spp. Mediated Plant Growth Promotion of Tomato Seedlings and Suppression of Meloidogyne incognita and Fusarium oxysporum Disease Complex - Ambreen Maqsood; Muhammad Naveed Aslam; Huma Khaliq; Muhammad Taimoor Shakeel; Haiyan Wu; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Impact of cement waste on soil fertility and crop productivity: a serious concern for food security - Junaid Iqbal; Muhammad Jamal Khan; Muhammad Hafeez; Junaid Ali Siddiqui; Muhammad Fahad; Bahar Ali; Muhammad Imran; Aqeel Ahmad; Shah Fahad (Environmental Science and Pollution Research, 2024)

Enhancing electricity distribution efficiency in Pakistan: A framework for progress and action - Fahad Bin Abdullah; Muhammad Arsalan Aqeeq; Rizwan Iqbal; Maria Abdullah; Falak Shad Memon (Utilities Policy, 2024)

Synthesis of polymeric ferrite composites (Ni-CoFe2O4/Chitosan, Zn-NiFe2O4/Starch, Co-NiZnFe2O4/Polyaniline, Ni doped CrZnFe2O4/Alginate, and Cr doped ZnCoFe2O4/PVA) for the removal of reactive golden yellow-160 dye from wastewater - Ghulam Mustafa; Ruba Munir; Bushra Sadia; Fazila Younas; Murtaza Sayed; Amna Muneer; Muhammad Fahad Sardar; Gadah Albasher; Saima Noreen (Journal of Environmental Chemical Engineering, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

Review of the potential pharmacological role of erucic acid: a monounsaturated omega-9 fatty acid - Imran Kazmi; Muhammad Afzal; Fahad A. Al-Abbasi; Shareefa A. AlGhamdi; Amira M. Alghamdi; Sami I. Alzarea; Waleed Hassan Almalki; Abeer S. AlGhamdi; Khadijah B. Alkinani; Nadeem Sayyed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Elevated Expression of YSL Genes and Enhanced Physiological Responses in Rice Subjected to Iron Application - Ammara Saleem; Asma Zulfiqar; Muhammad Zafar Saleem; Muhammad Hamzah Saleem; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Distribution of antibiotic resistant bacteria in different soil types following manure application - Tingting Song; Muhammad Fahad Sardar; Xuerong Wang; Binxu Li; Zhuoyi Zhang; Dimei Wu; Changxiong Zhu; Hongna Li (Soil Ecology Letters, 2024)

Soil fungal composition under decomposing deadwood is largely affected by tree bark density rather than soil properties - Li Fang; Yue Wang; Muhammad Fahad Sardar; Caixian Tang; Tao Fang; Jianhang Du; Enrong Yan; Qianqian Zhang; Yongchun Li (Applied Soil Ecology, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Exploring zeolite-based composites in adsorption and photocatalysis for toxic wastewater treatment: Preparation, mechanisms, and future perspectives - Iqra Liaquat; Ruba Munir; Naseer Ahmed Abbasi; Bushra Sadia; Amna Muneer; Fazila Younas; Muhammad Fahad Sardar; Muhammad Zahid; Saima Noreen (Environmental Pollution, 2024)

Silicon and Titanium Dioxide Mitigate Copper Stress in Wheat (Triticum aestivum L.) Through Regulating Antioxidant Defense Mechanisms - Rana M. Alshegaihi; Muhammad Hamzah Saleem; Ammara Saleem; Baber Ali; Humera Aziz; Shah Fahad; Abed Alataway; Ahmed Z. Dewidar; Hosam O. Elansary (Journal of Plant Growth Regulation, 2024)

Occurrence of toxic elements in river areas along drains and groundwater resources: source of contamination and associated health risk - Zahid Ullah; Fazila Younas; Aziz Ur Rahim Bacha; Abdur Rashid; Wedad A. Al-onazi; Muhammad Fahad Sardar (Environmental Monitoring and Assessment, 2024)

Soil microplastics: Impacts on greenhouse gasses emissions, carbon cycling, microbial diversity, and soil characteristics - Ismail Khan; Muhammad Tariq; Khulood Fahad Alabbosh; Abdul Rehman; Abdul Jalal; Asif Ali Khan; Muhammad Farooq; Guanlin Li; Babar Iqbal; Naveed Ahmad; Khalid Ali Khan; Daolin Du (Applied Soil Ecology, 2024)

Exploring Bacillus mycoides PM35 efficacy in enhancing rice (Oryza sativa L.) response to different types of microplastics through gene regulation and cellular fractionation - Dalal Nasser Binjawhar; Rana M. Alshegaihi; Aishah Alatawi; Muneefah Abdullah Alenezi; Abida Parveen; Muhammad Adnan; Baber Ali; Khalid Ali Khan; Shah Fahad; Eman Fayad (Environmental Science and Pollution Research, 2024)

Retraction Note: Impact of renewable energy consumption, financial development and natural resources on environmental degradation in OECD countries with dynamic panel data - Vishal Dagar; Muhammad Kamran Khan; Rafael Alvarado; Abdul Rehman; Muhammad Irfan; Oluwasegun B. Adekoya; Shah Fahad (Environmental Science and Pollution Research, 2024)

The groundbreaking impact of digitalization and artificial intelligence in sheep farming - Muhammad Furqan Arshad; Giovanni Pietro Burrai; Antonio Varcasia; Maria Francesca Sini; Fahad Ahmed; Giovanni Lai; Marta Polinas; Elisabetta Antuofermo; Claudia Tamponi; Raffaella Cocco; Andrea Corda; Maria Luisa Pinna Parpaglia (Research in Veterinary Science, 2024)

A fuzzy classification method based on rules learning for shaded and unshaded hotspot faults on photovoltaic modules - Junaid Ali Khan; Shengxue Tang; Borui Ji; Fahad Khan; Muhammad Adeel Khan; Usman Khan Khalil; Irshad Ullah (Journal of Cleaner Production, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Mapping groundwater potentiality by using hybrid machine learning models under the scenario of climate variability: a national level study of Bangladesh - Showmitra Kumar Sarkar; Fahad Alshehri; Shahfahad; Atiqur Rahman; Biswajeet Pradhan; Muhammad Shahab (Environment, Development and Sustainability, 2024)

Retraction Note: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Super capacity of ligand-engineered biochar for sorption of malachite green dye: key role of functional moieties and mesoporous structure - Muhammad Faheem; Muhammad Azher Hassan; Tariq Mehmood; Fahad Al-Misned; Nabeel Khan Niazi; Jianguo Bao; Jiangkun Du (Environmental Science and Pollution Research, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Promoting the suitability of graphitic carbon nitride and metal oxide nanoparticles: A review of sulfonamides photocatalytic degradation - Zakariyya Uba Zango; Muhammad Abubakar Lawal; Fahad Usman; Abdelmoneim Sulieman; Hanan Akhdar; M.H. Eisa; Osamah Aldaghri; Khalid Hassan Ibnaouf; Jun Wei Lim; Kuan Shiong Khoo; Yoke Wang Cheng (Chemosphere, 2024)

Sustainable production of bacterial flocculants by nylon-6,6 microplastics hydrolysate utilizing Brucella intermedia ZL-06 - Haijuan Zhao; Su Sun; Yongming Cui; Muhammad Wajid Ullah; Khulood Fahad Alabbosh; Noureddine Elboughdiri; Jiangang Zhou (Journal of Hazardous Materials, 2024)

Renewable energy and green economic growth nexus: Insights from simulated dynamic ARDL - Saira Ashfaq; Song Liangrong; Fahad Waqas; Saqib Gulzar; Ghulam Mujtaba; Rana Muhammad Nasir (Gondwana Research, 2024)

Electrokinetic technology enhanced the control of antibiotic resistance and the quality of swine manure composting - Binxu Li; Muhammad Fahad Sardar; Xu Zhang; Jing Ye; Yunlong Tian; Tingting Song; Xuerong Wang; Changxiong Zhu; Hongna Li (Chemical Engineering Journal, 2024)

Iron Oxide-Chitosan-Based Nanocomposite for Efficient Fluoride Removal From Drinking Water - Suraya Samejo; Jameel Ahmed Baig; Tasneem Gul Kazi; Hassan Imran Afridi; Saima Perveen; Muhammad Umer Frooq; Khalil Akhtar; Shakoor Ahmed Solangi; Fahad Abbasi; Sajjad Hussain (Water, Air, & Soil Pollution, 2024)

Harnessing Melatonin Protective Efficacy in Capsicum Plants Against Nickel-Contaminated Soil - Maryam M. Alomran; Ali Noman; Noreen Khalid; Naila Hadayat; Fatmah M. Alqahtani; Fahad Mohammed Alzuaibr; Noreen Akhter; Mohamed Hashem; Talaat Habeeb; Omar Mahmoud Al-Zoubi; Muhammad Aqeel (Journal of Soil Science and Plant Nutrition, 2024)

Correction to: Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Stochastic processes limit the effect of organic fertilizer application on soil bacterial community composition in salt marsh Suaeda salsa - Pengcheng Zhu; Chunyu Liu; Wei Wei; Yuxin Wu; Muhammad Fahad Sardar; Xiaona Yu; Weihua Guo (Journal of Cleaner Production, 2024)

Investigating biodiesel production from Chicken fat oil using bi-functional catalysts and microbubble mediated mass transfer - Maryam Asif; Fahad Javed; Muhammad Younas; Mazhar Amjad Gillani; William B. Zimmerman; Fahad Rehman (Fuel, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Trends and social aspects in the management and conversion of agricultural residues into valuable resources: A comprehensive approach to counter environmental degradation, food security, and climate change - Abbas Sheer; Muhammad Fahad Sardar; Fazila Younas; Pengcheng Zhu; Saima Noreen; Tariq Mehmood; Zia Ur Rahman Farooqi; Sidra Fatima; Weihua Guo (Bioresource Technology, 2024)

Integrated Use of Manure and Urea Fertilizer Economically Improve Wheat Production and Nitrogen Indices in a Range of Tillage Practices - Ihsan Muhammad; Jun Wang; Upendra M. Sainju; Ahmad Khan; Li Yang; Shakeel Ahmand; Yining Zhang; Shah Fahad; Xun Bo Zhou; Weijun Shen (Journal of Plant Growth Regulation, 2024)

Physiological and biochemical effects of biochar nanoparticles on spinach exposed to salinity and drought stresses - Aimun Rasheed; Sumera Anwar; Fahad Shafiq; Zaib-un-Nisa; Shahbaz Khan; Muhammad Ashraf (Environmental Science and Pollution Research, 2024)

Nitric oxide reduces cadmium uptake in wheat (Triticum aestivum L.) by modulating growth, mineral uptake, yield attributes, and antioxidant profile - Muhammad Nawaz; Muhammad Hamza Saleem; Muhammad Rehan Khalid; Baber Ali; Shah Fahad (Environmental Science and Pollution Research, 2024)

Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Assessment of future prediction of urban growth and climate change in district Multan, Pakistan using CA-Markov method - Sajjad Hussain; Muhammad Mubeen; Wajid Nasim; Faisal Mumtaz; Hazem Ghassan Abdo; Raoof Mostafazadeh; Shah Fahad (Urban Climate, 2024)

New insights on designing the next-generation materials for electrochemical synthesis of reactive oxidative species towards efficient and scalable water treatment: A review and perspectives - Amir Taqieddin; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh (Journal of Environmental Chemical Engineering, 2023)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

Exogenous Application of Silicon and Sulfate Improved Drought Tolerance in Sunflowers Through Modulation of Morpho-physiological and Antioxidant Defense Mechanisms - Muhammad Nisar; Muhammad Aqeel; Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Umair Rasheed; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Fahad Mohammed Alzuaibr; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Synthesis and Characterization of Cosmetic Grade Ionic Liquids and Their Application as Skin Whitening Agents - Farah Bashir; Nawshad Muhammad; Meshal Alshamrani; Maliha Uroos; Ahmad Salawi; Awaji Y. Safhi; Naveed Ahmed; Abdullah Alsalhi; Fahad Y. Sabei; Osama A. Madkhali (Journal of Pharmaceutical Innovation, 2023)

Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Saif Haider; Muhammad Umer Masood; Muhammad Rashid; Tauqeer Ali; Chaitanya B. Pande; Fahad Alshehri; Ismail Elkhrachy (Urban Climate, 2023)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Seasonal linkages between soil nitrogen mineralization and the microbial community in broadleaf forests with Moso bamboo (Phyllostachys edulis) invasion - Muhammad Fahad Sardar; Zhihao Chen; Caixian Tang; Shouke Zhang; Li Fang; Danni Miao; Yongfu Li; Qianqian Zhang; Yongchun Li (Science of The Total Environment, 2023)

RETRACTED: Effects of dumpsite leachate plumes on surface and groundwater and the possible public health risks - Joseph Omeiza Alao; Abubakar Fahad; Hazem Ghassan Abdo; Daniel A. Ayejoto; Hussin Almohamad; Muhammad Sani Ahmad; Mohammed Shettima Nur; Theophilus Toro Danjuma; Mumeen Adebayo Yusuf; Olaleye Timilehin Francis; Alao Ovaioza Joy (Science of The Total Environment, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Metal-Doped Carbon Dots (MCDs) as Efficient Nano-adsorbents for Detection, Monitoring, and Degradation of Wastewater Pollutants: Recent Progress, Challenges, and Future Prospects - Faheem Akhter; Jawad Ahmed; Munawar Ali Pinjaro; Fahad Ahmed Shaikh; Haris Jawad Arain; Muhammad Junaid Ahsan (Water, Air, & Soil Pollution, 2023)

Does the sampling of date palm fruits help in early detection of date palm mite, Oligonychus afrasiaticus (Acari: Tetranychidae)? - Fahad Jaber Alatawi; Jawwad Hassan Mirza; Kamal Al-Sahwan; Muhammad Kamran (Experimental and Applied Acarology, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

Introducing new green machining technology to enhance process performance and reduce environmental pollution in the metal processing industry - Pengwen Wang; Aqib Mashood Khan; Mohammed Alkahtani; Fahad Alasim; Muhammad Jamil; Ghulam Hussain (Environmental Science and Pollution Research, 2023)

Potential application of melatonin in reducing boron toxicity in rice seedlings through improved growth, cell wall composition, proline, and defense mechanisms - Xinyu Li; Muhammad Kamran; Muhammad Hamzah Saleem; Abdullah Ahmed Al-Ghamdi; Fahad M. Al-Hemaid; Mohamed S. Elshikh; Shaopeng Zhao; Muhammad Riaz (Chemosphere, 2023)

Microplastics in soil differentially interfere with nutritional aspects of chilli peppers - Khadiga Alharbi; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Fahad Mohammed Alzuaibr; Haifa AbdulAziz Sakit AlHaithloul; Noreen Akhter; Omar Mahmoud Al-Zoubi; Muhammad Qasim; Khalid M.Al Syaad; Manal Abdullah AlShaqhaa; et al. (South African Journal of Botany, 2023)

Progress in genome-wide identification of RBPs and their role in mitigating stresses, and growth in plants - Muhammad Haroon; Hala Tariq; Rabail Afzal; Muhammad Anas; Shanza Nasar; Neha Kainat; Sajid Fiaz; Uswa Irfan; Fahad Idrees; Muhammad Mubashar Zafar (South African Journal of Botany, 2023)

Synthesis, chracterization, and analytical application of silver dopamine magnetic nanomaterial - Rahat Nawaz; Zarayb Hussan; Fahad Ali; Naeem Akhtar; Batool Fatima; Muhammad Najam ul Haq; Awais Bokhari; Salman Raza Naqvi; Mohamed Ouladsmane; Saadat Majeed (Fuel, 2023)

Phenolic Compounds as a Quality Determinant of Grapes: A Critical Review - Muhammad Shahab; Sergio Ruffo Roberto; Muhammad Adnan; Shah Fahad; Renata Koyama; Muhammad Hamzha Saleem; Jamal Nasar; Shah Saud; Shah Hassan; Taufiq Nawaz (Journal of Plant Growth Regulation, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

In-situ hydrogen peroxide formation and persulfate activation over banana peel-derived biochar cathode for electrochemical water treatment in a flow reactor - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Kitae Baek; Akram N. Alshawabkeh (Chemosphere, 2023)

Testing the resource curse hypothesis: The dynamic roles of institutional quality, inflation and growth for Dragon - ShiYong Zheng; Hua Liu; Muhammad Hafeez; Xiaofeng Wang; Shah Fahad; Xiao-Guang Yue (Resources Policy, 2023)

An overview on human exposure, toxicity, solid-phase microextraction and adsorptive removal of perfluoroalkyl carboxylic acids (PFCAs) from water matrices - Zakariyya Uba Zango; Baranitharan Ethiraj; Fahad S. Al-Mubaddel; Mohammad Mahtab Alam; Muhammad Abubakar Lawal; Haliru Aivada Kadir; Kuan Shiong Khoo; Zaharaddeen Nasiru Garba; Fahad Usman; Muttaqa Uba Zango; Jun Wei Lim (Environmental Research, 2023)

Synthesis of efficient light harvesting Cr, N Co-doped TiO2 nanoparticles for enhanced visible light photocatalytic degradation of xanthene dyes; eosin yellow and rose bengal - Rida Tehreem; Muhammad Awais; Sanya Khursheed; Fahad Rehman; Dilshad Hussain; Young Sun Mok; Ghayas Uddin Siddiqui (Environmental Science and Pollution Research, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Physiological effects of some engineered nanomaterials on radish (Raphanus sativus L.) intercropped with pea (Pisum sativum L.) - Mehr-un-Nisa; Fahad Shafiq; Sumera Anwar; Arslan Mahmood; Muhammad Iqbal; Kaleem Ullah; Muhammad Zulqarnain; Imtiaz Haider; Muhammad Ashraf; Lixin Zhang (Environmental Science and Pollution Research, 2023)

A short review on the role of thyroxine in fast wound healing and tissue regeneration - Muhammad Fahad Amin; Muhammad Sarmad Zubair; Muhammad Ammar (Tissue and Cell, 2023)

Hydrothermal time analysis of mung bean (Vigna radiata (L.) Wilczek) seed germination at different water potential and temperatures - Fazal Amin; Sami Ullah; Shah Saud; Muhammad Zahid Ihsan; Shah Hassan; Sunjeet Kumar; Taufiq Nawaz; Matthew Tom Harrison; Ke Liu; Imran Khan; Haitao Liu; Khaled El-Kahtany; et al. (South African Journal of Botany, 2023)

Development of Mn-MOF/CuO composites as platform for efficient electrocatalytic OER - Bushra Shabbir; Nidhal Drissi; Karam Jabbour; Abdelaziz Gassoumi; F.F. Alharbi; Sumaira Manzoor; Muhammad Faheem Ashiq; H.A. Alburaih; Muhammad Fahad Ehsan; Muhammad Naeem Ashiq (Fuel, 2023)

Interactive Effects of Soil and Foliar-Applied Nanobiochar on Growth, Metabolites, and Nutrient Composition in Daucus carota - Habiba Khaliq; Sumera Anwar; Fahad Shafiq; Muhammad Ashraf; Lixin Zhang; Imtiaz Haider; Shahbaz Khan (Journal of Plant Growth Regulation, 2023)

An assessment of rural household vulnerability and resilience in natural hazards: evidence from flood prone areas - Shah Fahad; Mohammad Shakhawat Hossain; Nguyen Thi Lan Huong; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Rashid Naeem (Environment, Development and Sustainability, 2023)

Sedimentology and diagenesis impact on Sanduo formation (E2S) in Zhen 11 block of Gaoyou Sag, East China - Orkhan Isgandarov; Yang Shaochun; Muhammad Kashif; Zhang Yifan; Muhammad Fahad Ullah; Mohammed Saleh Ahmed Gaghman (Carbonates and Evaporites, 2023)

Ecological footprint, globalization, and economic growth: evidence from Asia - Saba Javeed; Hafiz Muhammad Abubakar Siddique; Fahad Javed (Environmental Science and Pollution Research, 2023)

Application of silicon and sodium hydrosulfide alleviates arsenic toxicity by regulating the physio-biochemical and molecular mechanisms of Zea mays - Aishah Alatawi; Manar Fawzi Bani Mfarrej; Rana M. Alshegaihi; Muhammad Ahsan Asghar; Sahar Mumtaz; Ghulam Yasin; Romina Alina Marc; Shah Fahad; Mohsen Mohamed Elsharkawy; Sadia Javed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Relating biogas technology and environmental impact assessment: a roadmap towards clean energy for environmental sustainability - Shahid Ali; Qingyou Yan; Muhammad Irfan; Shah Fahad (Environmental Science and Pollution Research, 2023)

Biocompatible cellulose acetate supported ammonium based ionic liquid membranes; way forward to remediate water pollution - Amina Khalid; Sana Zulfiqar; Noshabah Tabassum; Amir Sada Khan; Muhammad Amin Abid; Muhammad Saeed Akhtar; Fahad Al-Misned; Ahmed Muteb Aljuwayid; Sasan Zahmatkesh; Saira Asif (Chemosphere, 2023)

Interactive effects of polystyrene microplastics and Pb on growth and phytochemicals in mung bean (Vigna radiata L.) - Fu Chen; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Muhammad Usman Akbar; Fahad Mohammed Alzuaibr; Jing Ma; Ali Noman (Journal of Hazardous Materials, 2023)

Nano-silicon mediated alleviation of Cd toxicity by cell wall adsorption and antioxidant defense system in rice seedlings - Muhammad Riaz; Muhammad Kamran; Shah Fahad; Xiurong Wang (Plant and Soil, 2023)

Combined Effect of Rice-Straw Biochar and Humic Acid on Growth, Antioxidative Capacity, and Ion Uptake in Maize (Zea mays L.) Grown Under Saline Soil Conditions - Zaffar Malik; Natasha Malik; Iqra Noor; Muhammad Kamran; Aasma Parveen; Muhammad Ali; Freeha Sabir; Hosam O. Elansary; Tarek K. Zin El-Abedin; Eman A. Mahmoud; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Effect of Metals or Trace Elements on Wheat Growth and Its Remediation in Contaminated Soil - Iqbal Hussain; Sunnia Afzal; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Hamzah Saleem; Aishah Alatawi; Farukh Ameen; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Impact of eco-friendly chemical pretreatment on physicochemical and surface mechanical properties of sustainable lignocellulosic agricultural waste - Muhammad Sulaiman; Fahad Ali Rabbani; Tanveer Iqbal; Mohsin Ali Kazmi; Saima Yasin; M.A. Mujtaba; M.A. Kalam; Fares Almomani (Algal Research, 2023)

Going green: how do green supply chain management and green training influence firm performance? Evidence from a developing country - Naila Nureen; Yongrong Xin; Muhammad Irfan; Shah Fahad (Environmental Science and Pollution Research, 2023)

Assessing the impact of green tax reforms on corporate environmental performance and economic growth: do green reforms promote the environmental performance in heavily polluted enterprises? - Xiaohong Shi; Zeyuan Jiang; Dongbei Bai; Shah Fahad; Muhammad Irfan (Environmental Science and Pollution Research, 2023)

Removal of ceftriaxone sodium antibiotic from pharmaceutical wastewater using an activated carbon based TiO2 composite: Adsorption and photocatalytic degradation evaluation - Muneeb Abdullah; Javed Iqbal; Muhammad Saif Ur Rehman; Usman Khalid; Fahad Mateen; Salman Noshear Arshad; Abdullah G. Al-Sehemi; Hamed Algarni; Omar A. Al-Hartomy; Tahir Fazal (Chemosphere, 2023)

Different contributions of bacterial and fungal communities to nitrogen mineralization in Moso bamboo-invaded subtropical forests - Danni Miao; Xingyi Peng; Qiumei Teng; Muhammad Fahad Sardar; Qianqian Zhang; Xiangtao Zhu; Yongchun Li (Journal of Soils and Sediments, 2023)

Floating Treatment Wetlands (FTWs) is an Innovative Approach for the Remediation of Petroleum Hydrocarbons-Contaminated Water - Manar Fawzi Bani Mfarrej; Xiukang Wang; Muhammad Fahid; Muhammad Hamzah Saleem; Aishah Alatawi; Shafaqat Ali; Ghulam Shabir; Rehman Zafar; Muhammad Afzal; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Fullerenol [60] Nano-cages for Protection of Crops Against Oxidative Stress: A Critical Review - Fahad Shafiq; Muhammad Iqbal; Syed Hammad Raza; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Impacts of COVID-19 pandemic on environment, society, and food security - Hafiz Mohkum Hammad; Hafiz Muhammad Fasihuddin Nauman; Farhat Abbas; Rashid Jawad; Wajid Farhad; Muhammad Shahid; Hafiz Faiq Bakhat; Aitazaz A. Farooque; Muhammad Mubeen; Shah Fahad; Artemi Cerda (Environmental Science and Pollution Research, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

Abundance, spatial distribution, and characteristics of microplastics in agricultural soils and their relationship with contributing factors - Muhammad Amjad Khan; Qing Huang; Sardar Khan; Qingqing Wang; Jingjing Huang; Shah Fahad; Muhammad Sajjad; Yin Liu; Ondřej Mašek; Xiaohui Li; Junfeng Wang; Xiaomao Song (Journal of Environmental Management, 2023)

Individual and Synergic Effects of Phosphorus and Gibberellic Acid on Organic Acids Exudation Pattern, Ultra-Structure of Chloroplast and Stress Response Gene Expression in Cu-Stressed Jute (Corchorus Capsularis L.) - Aishah Alatawi; Xiukang Wang; Muhammad Hamzah Saleem; Muhammad Mohsin; Muzammal Rehman; Kamal Usman; Shah Fahad; Manar Fawzi Bani Mfarrej; Daniel Ingo Hefft; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Comparative Genetic Evaluation of Maize Inbred Lines at Seedling and Maturity Stages Under Drought Stress - Ali Shahzad; Hameed Gul; Muhammad Ahsan; Depeng Wang; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Nerium oleander could be used for sustainable management of traffic-borne elemental-enriched roadside soils - Noreen Khalid; Ali Noman; Atia Nazir; Aasma Tufail; Naila Hadayat; Fahad Mohammed Alzuaibr; Sobia Ikram; Noreen Akhter; Mumtaz Hussain; Muhammad Aqeel (Environmental Science and Pollution Research, 2023)

Implementing a novel deep learning technique for rainfall forecasting via climatic variables: An approach via hierarchical clustering analysis - Shah Fahad; Fang Su; Sufyan Ullah Khan; Muhammad Rashid Naeem; Kailei Wei (Science of The Total Environment, 2023)

Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor - Muhammad Younas; Sumeer Shafique; Abrar Faisal; Ainy Hafeez; Fahed Javed; Maria Mustafa; Fahad Rehman (Fuel, 2023)

Physiological and transcriptomic study reveal SeNPs-mediated AsIII stress detoxification mechanisms involved modulation of antioxidants, metal transporters, and transcription factors in Glycine max L. (Merr.) roots - Muhammad Zeeshan; Yu Xin Hu; Xiao Hong Guo; Chen Yu Sun; Abdul Salam; Shakeel Ahmad; Ihsan Muhammad; Jamal Nasar; Mohammad Shah Jahan; Shah Fahad; Xun Bo Zhou (Environmental Pollution, 2023)

A hybrid heuristic-driven technique to study the dynamics of savanna ecosystem - Muhammad Fawad Khan; Muhammad Sulaiman; Fahad Sameer Alshammari (Stochastic Environmental Research and Risk Assessment, 2023)

Effects of glycosylation on the accumulation and transport of fipronil in earthworm (Eisenia fetida) - Sukun Lin; Li Zhang; Peiwen Zhang; Rilin Huang; Muhammad Musa Khan; Shah Fahad; Dongmei Cheng; Zhixiang Zhang (Environmental Science and Pollution Research, 2023)

Assessment of greenhouse gases emissions, global warming potential and net ecosystem economic benefits from wheat field with reduced irrigation and nitrogen management in an arid region of China - Muhammad Kamran; Zhengang Yan; Irshad Ahmad; Qianmin Jia; Muhammad Usman Ghani; Xianjiang Chen; Shenghua Chang; Tengfei Li; Kadambot H.M. Siddique; Shah Fahad; Fujiang Hou (Agriculture, Ecosystems & Environment, 2023)

Air quality index prediction via multi-task machine learning technique: spatial analysis for human capital and intensive air quality monitoring stations - Xin Xiang; Shah Fahad; Myat Su Han; Muhammad Rashid Naeem; Shah Room (Air Quality, Atmosphere & Health, 2023)

Modeling the economic viability and performance of solar home systems: a roadmap towards clean energy for environmental sustainability - Shahid Ali; Qingyou Yan; Azer Dilanchiev; Muhammad Irfan; Shah Fahad (Environmental Science and Pollution Research, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Correction to: Ecological footprint of your denim jeans: production knowledge and green consumerism - Fahad Asmi; Qingyu Zhang; Muhammad Azfar Anwar; Kristina Linke; Younes Ben Zaied (Sustainability Science, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Molecular level characterization of DOM along a freshwater-to-estuarine coastal gradient in the Florida Everglades - Dennys Leyva; Rudolf Jaffé; Jessica Courson; John S. Kominoski; Muhammad Usman Tariq; Fahad Saeed; Francisco Fernandez-Lima (Aquatic Sciences, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

Determination and detoxification of aflatoxin and ochratoxin in maize from different regions of Pakistan - Syed Wajih ul Hassan Shah Gillani; Yumna Sadef; Muhammad Imran; Hafiz Muhammad Fahad Raza; Aamir Ghani; Sumera Anwar; Muhammad Yasin Ashraf; Shabbir Hussain (Environmental Monitoring and Assessment, 2022)

Ecological footprint of your denim jeans: production knowledge and green consumerism - Fahad Asmi; Qingyu Zhang; Muhammad Azfar Anwar; Kristina Linke; Younes Ben Zaied (Sustainability Science, 2022)

Geochemical investigation of low latitude black shale intervals of the Lower to Middle Jurassic succession, Indus Basin, Pakistan - Fahad Ali; Shiqi Zhang; Muhammad Hanif; Mohibullah Mohibullah; Yaxuan Zhang; Muhammad Usman; Sheng Wang; Xueliang Liu; Pengjie Ma; Dongmou Huang (Frontiers of Earth Science, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Pyroptosis in acute pancreatitis and its therapeutic regulation - Abdullah Al Mamun; Suzia Aktar Suchi; Md. Abdul Aziz; Muhammad Zaeem; Fahad Munir; Yanqing Wu; Jian Xiao (Apoptosis, 2022)

The Response of Triticum aestivum Treated with Plant Growth Regulators to Acute Day/Night Temperature Rise - Muhammad Zahid Ihsan; Abdul Khaliq; Manzer H. Siddiqui; Liaqat Ali; Ritesh Kumar; Hayssam M. Ali; Amar Matloob; Shah Fahad (Journal of Plant Growth Regulation, 2022)

The impact of COVID-19 pandemic on air pollution: a global research framework, challenges, and future perspectives - Khalid Mehmood; Sana Mushtaq; Yansong Bao; Saifullah; Sadia Bibi; Muhammad Yaseen; Muhammad Ajmal Khan; Muhammad Mohsin Abrar; Zaid Ulhassan; Shah Fahad; George P. Petropoulos (Environmental Science and Pollution Research, 2022)

Validation of in vitro grafting using indigenous wild grapevines as rootstock with commercial scion varieties - Fahad Nazir; Touqeer Ahmad; Muhammad Ajmal Bashir; Rizwan Rafique; Irfan Ali; Cristian Silvestri; Eddo Rugini; Sadar Uddin Siddiqui (Acta Physiologiae Plantarum, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Single nucleotide polymorphism based assessment of genetic diversity in local and exotic onion genotypes - Najma Tabussam; Rashid Mehmood Rana; Fahad Masoud Wattoo; Azeem Iqbal Khan; Rai Muhammad Amir; Talha Javed; Sunny Ahmar; Eldessoky S. Dessoky; Nader R. Abdelsalam (Molecular Biology Reports, 2022)

Influences of Long-term Crop Cultivation and Fertilizer Management on Soil Aggregates Stability and Fertility in the Loess Plateau, Northern China - Farhat Ullah Khan; Adnan Anwar Khan; Kai Li; Xuexuan Xu; Muhammad Adnan; Shah Fahad; Rafiq Ahmad; Mushtaq Ahmad Khan; Taufiq Nawaz; Faisal Zaman (Journal of Soil Science and Plant Nutrition, 2022)

Screening of Rice Cultivars for Nitrogen Use Efficiency and Yield Stability under Varying Nitrogen Levels - Weilu Wang; Liying Huang; Guanglong Zhu; Hao Zhang; Zhiqin Wang; Muhammad Adnan; Shah Saud; Zafar Hayat; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Structural, Biochemical, and Physiological Adjustments for Toxicity Management, Accumulation, and Remediation of Cadmium in Wetland Ecosystems by Typha domingensis Pers - Noreen Akhter; Omey Habiba; Mehwish Hina; Muhammad Muslim Shahnaz; Fahad Mohammed Alzuaibr; Saad Alamri; Mohamed Hashem; Noreen Khalid; Muhammad Aqeel; Ali Noman (Water, Air, & Soil Pollution, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Imaging of rupture process of 2005 Mw 7.6 Kashmir earthquake using back projection techniques - Mahmood Sultan; Farhan Javed; Muhammad Fahad Mahmood; Muhammad Ali Shah; Khawar Ashfaq Ahmed; Talat Iqbal (Arabian Journal of Geosciences, 2022)

The potential role of dietary plant ingredients against mammary cancer: a comprehensive review - Amjad Hussain; Marie-Lise Bourguet-Kondracki; Farhad Hussain; Abdur Rauf; Muhammad Ibrahim; Muhammad Khalid; Hidayat Hussain; Javid Hussain; Iftikhar Ali; Anees Ahmed Khalil; Fahad A. Alhumaydhi; Muhammad Khan; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Nanocrystals: Characterization Overview, Applications in Drug Delivery, and Their Toxicity Concerns - Mohammed Asadullah Jahangir; Syed Sarim Imam; Abdul Muheem; Ananda Chettupalli; Fahad A. Al-Abbasi; Muhammad Shahid Nadeem; Imran Kazmi; Muhammad Afzal; Sultan Alshehri (Journal of Pharmaceutical Innovation, 2022)

RETRACTED ARTICLE: Impact of renewable energy consumption, financial development and natural resources on environmental degradation in OECD countries with dynamic panel data - Vishal Dagar; Muhammad Kamran Khan; Rafael Alvarado; Abdul Rehman; Muhammad Irfan; Oluwasegun B. Adekoya; Shah Fahad (Environmental Science and Pollution Research, 2022)

Anti-Huntington’s Effect of Butin in 3-Nitropropionic Acid-Treated Rats: Possible Mechanism of Action - Sultan Alshehri; Fahad A. Al-Abbasi; Mohammed M. Ghoneim; Syed Sarim Imam; Muhammad Afzal; Khalid Saad Alharbi; Muhammad Shahid Nadeem; Nadeem Sayyed; Imran Kazmi (Neurotoxicity Research, 2022)

Genotypic Differences Among the Rice Genotypes to Arsenic Stress Cultivated Under Two Water Regimes: With an Inference to Human Health - Hafiz Faiq Bakhat; Sidra Arshad; Natasha; Sunaina Abbas; Ghulam Mustafa Shah; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Sajjad; Muhammad Ashfaq; Muhammad Shahid (Journal of Plant Growth Regulation, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Nitrification Inhibitor and Plant Growth Regulators Improve Wheat Yield and Nitrogen Use Efficiency - Khadim Dawar; Umar Rahman; Syed Sartaj Alam; Mohammad Tariq; Aamir Khan; Shah Fahad; Rahul Datta; Subhan Danish; Shah Saud; Muhammad Noor (Journal of Plant Growth Regulation, 2022)

Metabolic-based insecticide resistance mechanism and ecofriendly approaches for controlling of beet armyworm Spodoptera exigua: a review - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Xiaowei Li; Zhijun Zhang; Sakhawat Shah; Muhammad Imran; Mohammed A. Assiri; G. Mandela Fernández-Grandon; Nicolas Desneux; Muzammal Rehman; Shah Fahad; et al. (Environmental Science and Pollution Research, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Health concerns among waste collectors during pandemic crisis - Qing Ye; Fahad Asmi; Muhammad Azfar Anwar; Rongting Zhou; Ahmad Nabeel Siddiquei (Environmental Science and Pollution Research, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Ameliorative mechanisms of turmeric-extracted curcumin on arsenic (As)-induced biochemical alterations, oxidative damage, and impaired organ functions in rats - Anam Ishaq; Huma Gulzar; Ali Hassan; Muhammad Kamran; Muhammad Riaz; Aasma Parveen; Muhammad Sohaib Chattha; Noman Walayat; Sana Fatima; Sobia Afzal; Shah Fahad (Environmental Science and Pollution Research, 2021)

Impact of the mixture verses solo residue management and climatic conditions on soil microbial biomass carbon to nitrogen ratio: a systematic review - Ihsan Muhammad; Jun Wang; Ahmad Khan; Shakeel Ahmad; Li Yang; Izhar Ali; Muhammad Zeeshan; Saif Ullah; Shah Fahad; Shamsher Ali; Xun Bo Zhou (Environmental Science and Pollution Research, 2021)

Screening of wheat (Triticum aestivum L.) genotypes for drought tolerance using polyethylene glycol - Muhammad Adnan Bukhari; Adnan Noor Shah; Shah Fahad; Javaid Iqbal; Fahim Nawaz; Abdul Manan; Mohammad Safdar Baloch (Arabian Journal of Geosciences, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

Pollution characteristics and human health risk assessments of toxic metals and particle pollutants via soil and air using geoinformation in urbanized city of Pakistan - Khalid Mehmood; Yansong Bao; Roman Abbas; Saifullah; George P. Petropoulos; Hamaad Raza Ahmad; Muhammad Mohsin Abrar; Adnan Mustafa; Alwaseela Abdalla; Katia Lasaridi; Shah Fahad (Environmental Science and Pollution Research, 2021)

Melatonin-Induced Salinity Tolerance by Ameliorating Osmotic and Oxidative Stress in the Seedlings of Two Tomato (Solanum lycopersicum L.) Cultivars - Muhammad Ali; Muhammad Kamran; Ghulam Hassan Abbasi; Muhammad Hamzah Saleem; Salman Ahmad; Aasma Parveen; Zaffar Malik; Sobia Afzal; Sunny Ahmar; Khadim Muhammad Dawar; Sardar Ali; Saud Alamri; et al. (Journal of Plant Growth Regulation, 2021)

Strigolactone (GR24) Induced Salinity Tolerance in Sunflower (Helianthus annuus L.) by Ameliorating Morpho-Physiological and Biochemical Attributes Under In Vitro Conditions - Hira Zulfiqar; Muhammad Shahbaz; Muhammad Ahsan; Muhammad Nafees; Hammad Nadeem; Muhammad Akram; Ambreen Maqsood; Sunny Ahmar; Muhammad Kamran; Saud Alamri; Manzer H. Siddiqui; Shah Saud; et al. (Journal of Plant Growth Regulation, 2021)

Correction to: influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Microfacies analysis, depositional settings and reservoir investigation of Early Eocene Chorgali Formation exposed at Eastern Salt Range, Upper Indus Basin, Pakistan - Muhammad Fahad; Mumtaz Ali Khan; Jabir Hussain; Adeeb Ahmed; Mustafa Yar (Carbonates and Evaporites, 2021)

Nitrogen Fertilizer Effects on Microbial Respiration, Microbial Biomass, and Carbon Sequestration in a Mediterranean Grassland Ecosystem - Emre Babur; Ömer Süha Uslu; Martín Leonardo Battaglia; Muhammad Zahid Mumtaz; Subhan Danish; Shah Fahad; Andre Amakobo Diatta; Rahul Datta; Ekrem Ozlu (International Journal of Environmental Research, 2021)

Appraisal of iron accumulation in soil, forages, and blood plasma of sheep and goats: a case study in different districts of Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Kinza Wajid; Humayun Bashir; Muhammad Nadeem; Muhammad Fiaz Qamar; Muhammad Fahad Ullah; Saif Ur Rehman (Environmental Science and Pollution Research, 2021)

Role of sea-level pressure of Arabian Sea on variability of summer monsoon rainfall over Northern Pakistan - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal; Muhammad Adeel (Theoretical and Applied Climatology, 2021)

A review on nanofluid water alternating gas (N-WAG): application, preparation, mechanism, and challenges - Hassan Aziz; Temoor Muther; Muhammad Jawad Khan; Fahad I. Syed (Arabian Journal of Geosciences, 2021)

Silicon attenuates the negative effects of chromium stress in tomato plants by modifying antioxidant enzyme activities, ascorbate–glutathione cycle and glyoxalase system - Pravej Alam; Thamer H. Balawi; Fahad H. Altalayan; Ashraf Atef Hatamleh; Muhammad Ashraf; Parvaiz Ahmad (Acta Physiologiae Plantarum, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

Advances in Salt Tolerance of Some Major Fiber Crops Through Classical and Advanced Biotechnological Tools: A Review - Nudrat Aisha Akram; Fahad Shafiq; Muhammad Ashraf; Muhammad Iqbal; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2021)

α-Fe2O3-based nanocomposites: synthesis, characterization, and photocatalytic response towards wastewater treatment - Rooha Khurram; Zhan Wang; Muhammad Fahad Ehsan (Environmental Science and Pollution Research, 2021)

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Nexus on climate change: agriculture and possible solution to cope future climate change stresses - Aqeel Shahzad; Sana Ullah; Afzal Ahmed Dar; Muhammad Fahad Sardar; Tariq Mehmood; Muhammad Aammar Tufail; Awais Shakoor; Muhammad Haris (Environmental Science and Pollution Research, 2021)

Influence of semi-arid environment on radiation use efficiency and other growth attributes of lentil crop - Muhammad Habib ur Rahman; Ishfaq Ahmad; Depeng Wang; Shah Fahad; Muhammad Afzal; Abdul Ghaffar; Qaisar Saddique; Mehmood Alam Khan; Shah Saud; Shah Hassan; Muhammad Fahad; Mairaj Din; et al. (Environmental Science and Pollution Research, 2021)

Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Rhizosphere effect on removal and bioavailability of PAHs in contaminated agricultural soil - Na Li; Katarzyna Możdżeń; Zhiguo Zhang; Chong Liu; Peiman Zandi; Muhammad Fahad Sardar; Changxiong Zhu (Biologia, 2021)
The rhizosphere effect of ryegrass ( Lolium perenne L.) on polycyclic aromatic hydrocarbons (PAHs) dissipation, bioavailability and the structure change of microbial community was investigated using a compartmented device-rhizobox. The PAHs removal efficiency, bioavailability and the change in structure of the microbial community were ascertained using HPLC, Tenax-TA extraction and PCR-DGGE, respectively. The results showed that in the root area (R1) and bulk soil (CK), the removal of 3-ring PAHs were 97.72 ± 0.34% and 95.51 ± 0.75%, 4-ring PAHs were 89.01 ± 1.61% and 78.65 ± 0.47%, 5-ring PAHs were 77.64 ± 4.05% and 48.63 ± 3.19%, 6-ring PAHs were 68.69 ± 3.68% and 36.09 ± 1.78%, respectively. The average removal efficiency of the total PAHs after 80 days followed the order: R1M (91.1%) > CKM (84.9%) > CK (77.6%), indicating that planted soil with inoculation of Mycobacterium sp. as well as non-planted soil inoculated with Mycobacterium sp. could both significantly accelerate the removal of PAHs compared to control soil. The bioavailability ratio of PAHs with 3 and 4 rings tended to decrease (from 59.9% to 14.8% for 3-ring and 7.61% to 5.08% for 4-ring, respectively in R1) while those with 5 rings increased significantly (from 2.41% to 33.78% in R1) during the last 40 days, indicating that bioavailability alteration varies with the number of rings in the PAHs. In addition, PAH bioavailability generally did not show a significant difference between treated soil and control soil. These results suggest that ryegrass rhizosphere effect as well as inoculation of Mycobacterium sp. can accelerate PAH removal in polluted soil. The bacteria community structure demonstrated a complex interplay of soil, bacteria and ryegrass root, and potential PAH degraders were present in abundance. This study provides the exploring data of rhizosphere and bioaugmentation effect on PAH dissipation in agricultural soil, as well as the change of bioavailability and microbial composition thereof.

Two new life types and assessment of web-associated behavioral characteristics of some Oligonychus species on various host plants - Hafiz Muhammad Saqib Mushtaq; Muhammad Kamran; Fahad Jaber Alatawi (Experimental and Applied Acarology, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Higher biochar rate strongly reduced decomposition of soil organic matter to enhance C and N sequestration in nutrient-poor alkaline calcareous soil - Samar Fatima; Muhammad Riaz; Mohammad I. Al-Wabel; Muhammad Saleem Arif; Tahira Yasmeen; Qaiser Hussain; Mahnaz Roohi; Shah Fahad; Kawsar Ali; Muhammad Arif (Journal of Soils and Sediments, 2021)

Correction to: Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Assessment of European and hybrid aspen clones efficiency based on height growth and removal percentage of petroleum hydrocarbons—a field trial - Mir Md Abdus Salam; Muhammad Mohsin; Fahad Rasheed; Muhammad Ramzan; Zikria Zafar; Pertti Pulkkinen (Environmental Science and Pollution Research, 2020)
Soils polluted by organic or inorganic pollutants are an emerging global environmental issue due to their toxic effects. A phytoremediation experiment was conducted to evaluate the extraction potential of three European aspen clones (R2, R3, and R4) and seven hybrid aspen clones (14, 27, 34, 134, 172, 191, and 291) grown in soils polluted with hydrocarbons (includes polycyclic aromatic hydrocarbons (PAH) and total petroleum hydrocarbons (TPH)). Height growth, plant survival rates, and .hydrocarbon removal efficiencies were investigated over a 4-year period at a site in Somerharju, Luumaki Finland, to assess the remediation potential of the clones. Hydrocarbon content in the soil was determined by gas chromatography and mass spectrometry. The results revealed that hybrid aspen clones 14 and 34 and European aspen clone R3 achieved greater height growth (171, 171, and 114 cm, respectively) than the other clones in the study. Further, the greatest removals of PAH (90% at depth 10–50 cm) and (86% at depth 5–10 cm) were observed in plot G15 planted with clone R2. Furthermore, the greatest TPH removal rate at 5–10 cm depth (C 22 –C 40 , 97%; C 10 –C 40 , 96%; and C 10 –C 21 , 90%) was observed in plot 117 with clone 134. However, other clones demonstrated an ability to grow in soils with elevated levels of TPH and PAH, which indicates their tolerance to hydrocarbons and their potential capacity for phytoremediation of hydrocarbon-polluted soils. Our study suggests that European aspen and hybrid aspen clones could be used for the remediation of soils polluted with PAH and TPH.

Environmental concerns and switching toward electric vehicles: geographic and institutional perspectives - Aqsa Sajjad; Fahad Asmi; Jianxun Chu; Muhammad Azfar Anwar (Environmental Science and Pollution Research, 2020)

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

Foliar application of gibberellic acid endorsed phytoextraction of copper and alleviates oxidative stress in jute (Corchorus capsularis L.) plant grown in highly copper-contaminated soil of China - Muhammad Hamzah Saleem; Shah Fahad; Muhammad Adnan; Mohsin Ali; Muhammad Shoaib Rana; Muhammad Kamran; Qurban Ali; Inas A. Hashem; Parashuram Bhantana; Mubassir Ali; Reem M. Hussain (Environmental Science and Pollution Research, 2020)

Correction to: Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Sedimentology of Shahejie Formation, Bohai Bay Basin: a case study of Es1 member in Nanpu Sag - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Faisal Rehman; Kamran Shehzad; Muhammad Fahad Ullah; Ghulam Mustafa (Carbonates and Evaporites, 2020)

Asymmetric effects of energy efficiency and renewable energy on carbon emissions of BRICS economies: evidence from nonlinear panel autoregressive distributed lag model - Rabia Akram; Muhammad Tariq Majeed; Zeeshan Fareed; Fahad Khalid; Chengang Ye (Environmental Science and Pollution Research, 2020)

Short stay, long impact: ecological footprints of sojourners - Qing Ye; Muhammad Azfar Anwar; Rongting Zhou; Fahad Asmi; Intikhab Ahmad (Environmental Science and Pollution Research, 2020)

Foliar applied fullerol differentially improves salt tolerance in wheat through ion compartmentalization, osmotic adjustments and regulation of enzymatic antioxidants - Fahad Shafiq; Muhammad Iqbal; Muhammad Arslan Ashraf; Muhammad Ali (Physiology and Molecular Biology of Plants, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

Seed Pre-treatment with Polyhydroxy Fullerene Nanoparticles Confer Salt Tolerance in Wheat Through Upregulation of H2O2 Neutralizing Enzymes and Phosphorus Uptake - Fahad Shafiq; Muhammad Iqbal; Muhammad Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2019)

Alpha-Tocopherol-Induced Regulation of Growth and Metabolism in Plants Under Non-stress and Stress Conditions - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf; Fahad Al-Qurainy; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2019)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

Physiological response of spinach to toxic heavy metal stress - Muhammad Zubair; Qudrat Ullah Khan; Nosheen Mirza; Rizwana Sarwar; Asghar Ali Khan; Mohammad Safdar Baloch; Shah Fahad; Adnan Noor Shah (Environmental Science and Pollution Research, 2019)

Long-term ENSO relationship to precipitation and storm frequency over western Himalaya–Karakoram–Hindukush region during the winter season - Shahzad Kamil; Mansour Almazroui; In-Sik Kang; Muhammad Hanif; Fred Kucharski; Muhammad Adnan Abid; Fahad Saeed (Climate Dynamics, 2019)

Climate change communication as political agenda and voters’ behavior - Muhammad Azfar Anwar; Rongting Zhou; Aqsa Sajjad; Fahad Asmi (Environmental Science and Pollution Research, 2019)

Spatial heterogeneity of ecosystem services: a distance decay approach to quantify willingness to pay for improvements in Heihe River Basin ecosystems - Sufyan Ullah Khan; Imran Khan; Minjuan Zhao; Hsiaoping Chien; Qian Lu; Muhammad Abu Sufyan Ali; Arshad Ahmad Khan; Shah Fahad (Environmental Science and Pollution Research, 2019)

Trehalose: A Key Organic Osmolyte Effectively Involved in Plant Abiotic Stress Tolerance - Firdos Kosar; Nudrat Aisha Akram; Muhammad Sadiq; Fahad Al-Qurainy; Muhammad Ashraf (Journal of Plant Growth Regulation, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Estimation and exposure concentration of trihalomethanes (THMs) and its human carcinogenic risk in supplied pipeline water of Dhaka City, Bangladesh - Fahad Ahmed; Tanzir Ahmed Khan; Abu Naieum Muhammad Fakhruddin; Mohammad Mahfuzur Rahman; Reaz Mohammad Mazumdar; Shamim Ahmed; Mohammad Toufick Imam; Mohammod Kabir; Abu Tareq Mohammad Abdullah (Environmental Science and Pollution Research, 2019)

Performance of Aeluropus lagopoides (mangrove grass) ecotypes, a potential turfgrass, under high saline conditions - Muhammad Zamin; Abdul Mateen Khattak; Abdul Mohsin Salim; Kenneth B. Marcum; Muhammad Shakur; Shahen Shah; Ibadullah Jan; Shah Fahad (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2019)

Detection of mineral alteration induced by hydrocarbon microseepages by using remotely sensed data in the Fateh Jang area of the Northern Potwar region of Pakistan - Ayesha Habib; Muhammad Khubaib Abuzar; Ijaz Ahmad; Urooj Shakir; Syed Amer Mahmood; Mumtaz Ali Khan; Muhammad Fahad Mahmood (Arabian Journal of Geosciences, 2019)

Morpho-physiological and biochemical responses of tolerant and sensitive rapeseed cultivars to drought stress during early seedling growth stage - Mohammad Nauman Khan; Jing Zhang; Tao Luo; Jiahuan Liu; Fei Ni; Muhammad Rizwan; Shah Fahad; Liyong Hu (Acta Physiologiae Plantarum, 2019)

Natural and synthetic estrogens in leafy vegetable and their risk associated to human health - Muhammad Adeel; Muhammad Zain; Shah Fahad; Muhammad Rizwan; Asif Ameen; Hao Yi; Mansoor A. Baluch; Jie Yinn Lee; Yukui Rui (Environmental Science and Pollution Research, 2018)

Developing nonlinear models for sediment load estimation in an irrigation canal - Fahad Ahmed; Muhammad Hassan; Hashim Nisar Hashmi (Acta Geophysica, 2018)

Phytohormones enhanced drought tolerance in plants: a coping strategy - Abid Ullah; Hakim Manghwar; Muhammad Shaban; Aamir Hamid Khan; Adnan Akbar; Usman Ali; Ehsan Ali; Shah Fahad (Environmental Science and Pollution Research, 2018)

Coal mining trends, approaches, and safety hazards: a brief review - Muhammad Fahad Ullah; Abdullah M. Alamri; Khalid Mehmood; Mian Sohail Akram; Faisal Rehman; Saif Ur Rehman; Omar Riaz (Arabian Journal of Geosciences, 2018)

Yield Forecasting of Spring Maize Using Remote Sensing and Crop Modeling in Faisalabad-Punjab Pakistan - Ishfaq Ahmad; Umer Saeed; Muhammad Fahad; Asmat Ullah; M. Habib ur Rahman; Ashfaq Ahmad; Jasmeet Judge (Journal of the Indian Society of Remote Sensing, 2018)

Webbing life type and behavioral response of the date palm mite, Oligonychus afrasiaticus, to webbing residues on leaves and fruits of date palm - Jawwad Hassan Mirza; Muhammad Kamran; Fahad Jaber Alatawi (Experimental and Applied Acarology, 2018)

Influence of Siberian High on temperature variability over northern areas of South Asia - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal; Mirza Jawwad Baig (Meteorology and Atmospheric Physics, 2018)

Response of the predatory mite Cydnoseius negevi (Acari: Phytoseiidae) to webbing of the date palm mite, Oligonychus afrasiaticus (Acari: Tetranychidae), on date palm fruits and leaves - Jawwad Hassan Mirza; Muhammad Kamran; Fahad Jaber Alatawi (Experimental and Applied Acarology, 2018)

Determination of groundwater potential by using geoelectrical method and petrographic analysis in Rawalakot and adjacent areas of Azad Kashmir, sub-Himalayas, Pakistan - Abrar Niaz; Muhammad Rustam Khan; Umer Ijaz; Muhammad Yasin; Fahad Hameed (Arabian Journal of Geosciences, 2018)

Influence of composted poultry manure and irrigation regimes on some morpho-physiology parameters of maize under semiarid environments - Wajid Farhad; Mumtaz Akhtar Cheema; Hafiz Mohkum Hammad; Muhammad Farrukh Saleem; Shah Fahad; Farhat Abbas; Ikramullah Khosa; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2018)

Determination and estimation of magnesium content in the single phase magnesium-calcite [Ca(1−x)MgxCO3(s)] using electron probe micro-analysis (EPMA) and X-ray diffraction (XRD) - Muhammad Fahad; Sundas Saeed (Geosciences Journal, 2018)

Current status and future possibilities of molecular genetics techniques in Brassica napus - Muhammad Afzal; Salem Safer Alghamdi; Muhammad Habib ur Rahman; Awais Ahmad; Tahir Farooq; Mukhtar Alam; Imtiaz Ali Khan; Hidayat Ullah; Wajid Nasim; Shah Fahad (Biotechnology Letters, 2018)

Application of gravity and magnetic methods for the crustal study and delineating associated ores in the western limb of Hazara Kashmir Syntaxis, Northwest Himalayas, Pakistan - Muhammad Rustam Khan; Shahid Saleem Bilali; Fahad Hameed; Awais Rabnawaz; Sohail Mustafa; Naveed Azad; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Aminolevulinic acid and nitric oxide regulate oxidative defense and secondary metabolisms in canola (Brassica napus L.) under drought stress - Nudrat Aisha Akram; Majid Iqbal; Atta Muhammad; Muhammad Ashraf; Fahad Al-Qurainy; Sidra Shafiq (Protoplasma, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Singular value decomposition analysis for examining the impact of Siberian High on winter precipitation variability over South Asia - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal (Theoretical and Applied Climatology, 2017)

Nitrogen nutrition in cotton and control strategies for greenhouse gas emissions: a review - Aziz Khan; Daniel Kean Yuen Tan; Fazal Munsif; Muhammad Zahir Afridi; Farooq Shah; Fan Wei; Shah Fahad; Ruiyang Zhou (Environmental Science and Pollution Research, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Water Deficit Irrigation and Nitrogen Response of Sudan Grass under Arid Land Drip Irrigation Conditions - Samir G. Al‐Solaimani; Fahad Alghabari; Muhammad Zahid Ihsan; Shah Fahad (Irrigation and Drainage, 2017)
The present study evaluated the interactive effect of water deficit irrigation (WDI) and nitrogen application on Sorghum sudanense growth, biomass accumulation, nitrogen content and water productivity for two consecutive seasons and three cuts. The WDI of 50, 30 and 10% depletion ratios (different application rate and frequency) along with four levels (0, 100, 200 and 300 kg ha −1 ) of nitrogen fertilizer were applied in three splits. The WDI of 10% depletion ratio recorded significantly higher (15–17%) fresh and dry biomass accumulation of both leaf and stem as compared with WDI of 50%. Nitrogen application improved all growth traits irrespective of the applied levels of WDI, season and cut number. The interaction of WDI of 30% depletion ratio and N200 outcompeted all other treatments for plant nitrogen and protein contents, as the resulting increment was 10–22% higher as compared to control. Of the different cut numbers, the first cutting ascribed the maximum value for plant protein contents and stated up to 32% improvement over second and third cuttings. By increasing the rate of nitrogen application, a significant increment in crop water productivity was also measured that attributed at least a threefold higher value for stem over leaf. In essence, WDI of 10% depletion ratio and nitrogen rate of 200 kg ha −1 were the optimum levels that improved Sudan grass growth, biomass and water use efficiency; moreover, the 30% depletion ratio favoured plant nitrogen content. By using a WDI approach, we can improve our forage yield with a limited amount of water by increasing irrigation frequency. Copyright © 2017 John Wiley & Sons, Ltd.

Nitrogen fertility and abiotic stresses management in cotton crop: a review - Aziz Khan; Daniel Kean Yuen Tan; Muhammad Zahir Afridi; Honghai Luo; Shahbaz Atta Tung; Mir Ajab; Shah Fahad (Environmental Science and Pollution Research, 2017)

Environment polluting conventional chemical control compared to an environmentally friendly IPM approach for control of diamondback moth, Plutella xylostella (L.), in China: a review - Muhammad Shakeel; Muhammad Farooq; Wajid Nasim; Waseem Akram; Fawad Zafar Ahmad Khan; Waqar Jaleel; Xun Zhu; Haichen Yin; Shuzhong Li; Shah Fahad; Saddam Hussain; Bhagirath Singh Chauhan; et al. (Environmental Science and Pollution Research, 2017)

Water-saving technologies affect the grain characteristics and recovery of fine-grain rice cultivars in semi-arid environment - Khawar Jabran; Muhammad Riaz; Mubshar Hussain; Wajid Nasim; Umar Zaman; Shah Fahad; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

Agroforestry: a sustainable environmental practice for carbon sequestration under the climate change scenarios—a review - Farhat Abbas; Hafiz Mohkum Hammad; Shah Fahad; Artemi Cerdà; Muhammad Rizwan; Wajid Farhad; Sana Ehsan; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2017)

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review - Hafiz Faiq Bakhat; Zahida Zia; Shah Fahad; Sunaina Abbas; Hafiz Mohkum Hammad; Ahmad Naeem Shahzad; Farhat Abbas; Hesham Alharby; Muhammad Shahid (Environmental Science and Pollution Research, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Metamorphic temperature investigation of coexisting calcite and dolomite marble––examples from Nikani Ghar marble and Nowshera Formation, Peshawar Basin, Pakistan - Muhammad Fahad; Yaseen Iqbal; Mohammad Riaz; Rick Ubic; Simon A. T. Redfern (Journal of Earth Science, 2016)

Tectonic study of the Sub-Himalayas based on geophysical data in Azad Jammu and Kashmir and northern Pakistan - Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Muhammad Basharat; Sohail Mustafa (Journal of Earth Science, 2016)

Protein profiling analysis of Gossypium hirsutum (Malvales: Malvaceae) leaves infested by cotton whitefly Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Ibrahim; Sumaira Yasmeen; Ghanva Zaman; Li Bin; Fahad Al-Qurainy; Habib-ur-Rehman Athar; Kausar Hussain Shah; Muhammad Khurshid; Muhammad Ashraf (Applied Entomology and Zoology, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Influence of sub-lethal crude oil concentration on growth, water relations and photosynthetic capacity of maize (Zea mays L.) plants - Habib-ur-Rehman Athar; Sarah Ambreen; Muhammad Javed; Mehwish Hina; Sumaira Rasul; Zafar Ullah Zafar; Hamid Manzoor; Chukwuma C. Ogbaga; Muhammad Afzal; Fahad Al-Qurainy; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Petrology and geochemistry of Jura granite and granite gneiss in the Neelum Valley, Lesser Himalayas (Kashmir, Pakistan) - Muhammad Saleem Mughal; Muhammad Sabir Khan; Muhammad Rustam Khan; Sohail Mustafa; Fahad Hameed; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2016)

Economic assessment of different mulches in conventional and water-saving rice production systems - Khawar Jabran; Mubshar Hussain; Shah Fahad; Muhammad Farooq; Ali Ahsan Bajwa; Hesham Alharrby; Wajid Nasim (Environmental Science and Pollution Research, 2016)

Evaluation of source rocks using one dimensional maturity modeling in Lower Indus Basin, Pakistan - Faisal Qayyum; Muhammad Hanif; Muhammad Mujtaba; Sohail Wahid; Fahad Ali (Arabian Journal of Geosciences, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Geotechnical study of marble, schist, and granite as dimension stone: a case study from parts of Lesser Himalaya, Neelum Valley Area, Azad Kashmir, Pakistan - Sohail Mustafa; Muhammad Arshad Khan; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Aamir Asghar; Abrar Niaz (Bulletin of Engineering Geology and the Environment, 2015)

Effect of Rht alleles on wheat grain yield and quality under high temperature and drought stress during booting and anthesis - Fahad Alghabari; Muhammad Zahid Ihsan; Saddam Hussain; Ghulam Aishia; Ihsanullah Daur (Environmental Science and Pollution Research, 2015)

Genetic analysis suggests a shared origin of Punica granatum cultivars in Oman with cultivars from the center of origin, Iran - Abdullah M. Al-Sadi; Ahmed R. AL-Fahdi; Rashid A. Al-Yahyai; Aisha G. Al-Ghaithi; Fahad A. Al-Said; Muhammad J. Soleiman (Genetic Resources and Crop Evolution, 2015)

Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Fahad Irfan Siddiqui; Dur Muhammad Pathan; Syed Baharom Azhar Bin Syed Osman; Munawar Ali Pinjaro; Safiullah Memon (Arabian Journal of Geosciences, 2015)

Using larger benthic foraminifera for the paleogeographic reconstruction of Neo-Tethys during Paleogene - Sajjad Ahmad; Wahid Jalal; Fahad Ali; Muhammad Hanif; Zaheen Ullah; Suleman Khan; Asghar Ali; Irfan U. Jan; Khaista Rehman (Arabian Journal of Geosciences, 2015)

Potential role of phytohormones and plant growth-promoting rhizobacteria in abiotic stresses: consequences for changing environment - Shah Fahad; Saddam Hussain; Asghari Bano; Shah Saud; Shah Hassan; Darakh Shan; Faheem Ahmed Khan; Fahad Khan; Yutiao Chen; Chao Wu; Muhammad Adnan Tabassum; Ma Xiao Chun; et al. (Environmental Science and Pollution Research, 2015)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

Synthesis, docking studies, and in silico ADMET predictions of some new derivatives of pyrimidine as potential KSP inhibitors - Umer Rashid; Syed Fahad Hassan; Samina Nazir; Abdul Wadood; Muhammad Waseem; Farzana Latif Ansari (Medicinal Chemistry Research, 2015)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

Erratum to: The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

Therapeutic exploration of betulinic acid in chemically induced hypothyroidism - Muhammad Afzal; Imran Kazmi; Susmita Semwal; Fahad A. Al-Abbasi; Firoz Anwar (Molecular and Cellular Biochemistry, 2014)

Combination of sulfamethoxazole and selenium in anticancer therapy: a novel approach - Ritu Gupta; Imran Kazmi; Muhammad Afzal; Ruqaiyah Khan; Mohit Chauhan; Fahad A. Al-Abbasi; Aftab Ahmad; Firoz Anwar (Molecular and Cellular Biochemistry, 2013)

Anticancer effect of ursolic acid stearoyl glucoside in chemically induced hepatocellular carcinoma - Imran Kazmi; Anil Raj Narooka; Muhammad Afzal; Rajbala Singh; Fahad A. Al-Abbasi; Aftab Ahmad; Firoz Anwar (Journal of Physiology and Biochemistry, 2013)

Antiproliferative potential of sarcophine and its semisynthetic sulfur-containing derivatives against human mammary carcinoma cell lines - Jamal M. Arif; Swapnali S. Sawant; Khalid A. El Sayed; Muhammad Kunhi; Manogaran P. Subramanian; Yunus M. Siddiqui; Diaa T. A. Youssef; Khalid Al-Hussain; Mohammed N. Al-Ahdal; Fahad Al-Khodairy (Journal of Natural Medicines, 2007)